Dispersion, method for producing structure with conductive pattern using the same, and structure with conductive pattern

A dispersion of copper oxide, dispersant, and reducing agent forms a conductive pattern with low resistance and improved stability, addressing the challenges of existing direct wiring printing technologies by enhancing dispersion stability and solderability, applicable to both thin and thick films.

CN114512265BActive Publication Date: 2024-12-31ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210194921.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-02-13
Filing Date
2018-03-15
Publication Date
2024-12-31
Estimated Expiration
2038-03-15

AI Technical Summary

Technical Problem

Existing direct wiring printing technologies using metal devices capable of effectively forming a conductive pattern on a substrate have not addressed the need for a substrate have issues with metal thin films that require numerous steps, complicated methods, and the use of photoresist materials, and face challenges such as high resistivity, oxidation, crack formation, and poor solderability, especially with copper oxide particles.

Method used

A dispersion containing copper oxide, a dispersant, and a reducing agent within specific mass ratios, combined with copper particles of varying shapes, is used to form a conductive pattern through methods like screen printing and laser irradiation, promoting sintering and reducing resistivity while maintaining dispersion stability.

Benefits of technology

The solution results in a conductive pattern with low resistance, excellent temporal stability, and improved solderability, suitable for both thin and thick films, using existing screen printing devices without photoresist materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114512265B_ABST
    Figure CN114512265B_ABST
Patent Text Reader

Abstract

The present invention relates to a dispersion and a method for manufacturing a structure with a conductive pattern using the dispersion and a structure with a conductive pattern, and provides a dispersion having high dispersion stability and forming a conductive pattern with low resistance on a substrate. The dispersion (1) contains copper oxide (2), a dispersant (3), and a reducing agent, wherein the content of the reducing agent is within the range of the following formula (1), and the content of the dispersant is within the range of the following formula (2). By including the reducing agent, the reduction of copper oxide to copper is promoted during firing, thereby promoting the sintering of copper. 0.0001≦(reducing agent mass / copper oxide mass)≦0.10(1)0.0050≦(dispersant mass / copper oxide mass)≦0.30(2).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The Chinese national application number of the application to which it is directed is 201880013603.1, the international application number is PCT / JP2018 / 010287, the application date is March 15, 2018, the date of entry into China is August 13, 2019, and the name of the invention is "Dispersion and method for manufacturing a structure with a conductive pattern using the same, and structure with a conductive pattern". Technical Field

[0002] The present invention relates to a dispersion, a method for producing a structure with a conductive pattern using the dispersion, and a structure with a conductive pattern. Background Art

[0003] The circuit substrate has a structure in which conductive wiring is applied on a substrate. The manufacturing method of the circuit substrate is generally as follows. First, a photoresist is applied to a substrate on which a metal foil is attached. Next, the photoresist is exposed and developed to obtain a bottom plate shape of a desired circuit pattern. After that, the metal foil not covered by the photoresist is removed by chemical etching to form a pattern. In this way, a high-performance circuit substrate can be manufactured.

[0004] However, the conventional method has disadvantages such as requiring many steps, being complicated, and requiring a photoresist material.

[0005] In contrast, direct wiring printing technology (hereinafter referred to as PE (printed electronics) method) has attracted attention by using a dispersion in which particles selected from the group consisting of metal particles and metal oxide particles are dispersed to directly print a desired wiring pattern on a substrate. This technology has a small number of steps and does not require the use of photoresist materials, and has extremely high productivity.

[0006] As dispersions, metal ink and metal paste can be cited. Metal ink is a dispersion formed by metal ultrafine particles with an average particle size of several nanometers to tens of nanometers dispersed in a dispersion medium. When the metal ink is applied to a substrate and dried and then heat-treated, due to the unique melting point lowering effect of the metal ultrafine particles, it can be sintered at a temperature lower than the melting point of the metal to form a conductive metal film (hereinafter also referred to as a conductive film). The metal film obtained using the metal ink has a thin film thickness close to that of a metal foil.

[0007] On the other hand, metal paste is a dispersion formed by dispersing micron-sized metal particles together with a binder resin in a dispersion medium. Since the size of the particles is large, in order to prevent sedimentation, they are usually supplied in a state of relatively high viscosity. Therefore, it is suitable to be coated using screen printing or a dispenser suitable for materials with high viscosity. The size of the metal particles in the metal paste is large, so it has the characteristic of being able to form a thicker metal film.

[0008] Copper has attracted attention as a metal used in such metal particles. In particular, copper is the most promising material as a substitute for ITO (indium tin oxide), which is widely used as an electrode material for projection-type electrostatic capacitive touch panels, from the perspectives of resistivity, ion (electrochemical) migration, performance as a conductor, price, reserves, etc.

[0009] However, copper is easily oxidized when it is ultrafine particles of several tens of nanometers, and therefore needs to be subjected to an anti-oxidation treatment. The anti-oxidation treatment has the problem of hindering sintering.

[0010] In order to solve such problems, it has been proposed to use ultrafine particles of copper oxide as a precursor and reduce the copper oxide to copper using energy such as heat or active light in a suitable atmosphere to form a copper thin film (for example, see Patent Document 1).

[0011] Since the surface diffusion in the ultrafine particles of copper oxide itself occurs at a temperature below 300°C, when the copper oxide is reduced to copper using energy in an appropriate atmosphere, the copper ultrafine particles sinter with each other to form dense random chains, forming a network as a whole, thereby obtaining the desired electrical conductivity.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: International Publication No. 2003 / 051562 Summary of the invention

[0015] Problems to be solved by the invention

[0016] As a first problem, the metal thin film obtained by the PE method using metal ink and metal paste is required to have not only low resistivity but also little change over time. For example, with respect to silver paste, it is known that silver is easily oxidized in the atmosphere, and the resistivity increases after oxidation, so the resistivity between silver particles deteriorates over time.

[0017] However, regarding the metal film obtained by the PE method using ultrafine particles of copper oxide disclosed in Patent Document 1 as a precursor, there is no research on the stability of resistivity in the prior art documents.

[0018] In addition, in industrial applications, dispersions are also required to have excellent dispersion stability with respect to temporal changes at high concentrations.

[0019] In addition, as the second topic, it is known that in the existing PE method using a metal paste in which metal oxide particles are metallized by reduction to obtain a metal film, the smaller the particle size, the easier it is to sinter, cracks are generated during the sintering process, and the resistivity is easily reduced. By sintering, the interface of a plurality of particles in contact fuses, and grows into large particles by entering each other. At this time, the surface area of ​​the particles decreases, and the gaps between the plurality of particles disappear. As a result, the volume of the coating shrinks, and cracks may occur for this reason. Such cracks cause the rise of the resistivity of the metal film.

[0020] It is also known that when the thickness of the coating film of the metal paste exceeds 1 μm, cracks are easily generated during the firing process and cracks are generated over time, and the resistivity of the metal film deteriorates over time.

[0021] However, regarding the metal film obtained by the PE method using ultrafine particles of copper oxide disclosed in Patent Document 1 as a precursor, there is no research on the temporal stability of resistivity, particularly the generation of cracks over time, in the prior art documents.

[0022] Furthermore, the dispersion used in the PE method is required to be applicable not only to inkjet printing for obtaining a relatively thin coating film but also to screen printing for obtaining a relatively thick coating film.

[0023] In addition, the metal film is also required to be easy to solder. For example, in common general-purpose conductive pastes, the electrical conduction is achieved by physical contact of metal particles (average particle size 0.5 to 2.0 μm) through the effective shrinkage of the binder resin. Therefore, the binder resin seeps out on the surface of the metal film to form a coating, which makes soldering difficult. In addition, the metal film is also required to have high adhesion to the solder.

[0024] The present invention has been made in view of this point, and one of its objects is to provide a dispersion having high dispersion stability and capable of forming a conductive pattern with low resistance on a substrate, a method for producing a structure with a conductive pattern using the dispersion, and a structure with a conductive pattern.

[0025] Another object is to provide a dispersion that can be applied to a screen printing method and can provide a conductive pattern having excellent temporal stability of resistivity and solderability, a method for producing a structure having a conductive pattern using the dispersion, and a structure having a conductive pattern.

[0026] Means for solving problems

[0027] The present inventors have conducted intensive studies to solve the above problems and have completed the present invention. The present invention is to solve any one of the first to third problems.

[0028] That is, the dispersion according to one embodiment of the present invention contains copper oxide, a dispersant, and a reducing agent, wherein the content of the reducing agent is within the range of the following formula (1), and the content of the dispersant is within the range of the following formula (2).

[0029] 0.0001≦(reducing agent mass / copper oxide mass)≦0.10(1)

[0030] 0.0050≦(dispersant mass / copper oxide mass)≦0.30(2)

[0031] According to this configuration, by limiting the mass range of the reducing agent and the dispersant relative to the copper oxide, the dispersion stability is improved, and the resistance of the conductive pattern is effectively reduced. In addition, since the firing treatment can be performed using plasma or light or laser, the organic matter in the copper oxide is decomposed, the firing of the copper oxide is promoted, and a conductive pattern with low resistance can be formed.

[0032] A dispersion according to one embodiment of the present invention is characterized in that it contains copper oxide having a particle size of 1 nm to 50 nm, copper particles having a particle size of 0.1 μm to 100 μm, and an organic compound having a phosphoric acid group.

[0033] According to this configuration, when a coating film obtained by using a dispersion containing copper particles having a micron-sized particle size and nanometer-sized copper oxide particles is sintered by a sintering treatment, the copper particles are bonded to each other to form a strong mechanical structure. At the same time, the copper oxide particles existing between the copper particles are reduced by the sintering treatment and changed into metallic copper and sintered at the same time, and are integrated with the copper particles to generate electrical conduction, thereby improving the mechanical strength and electrical conduction of the conductive pattern, and improving the time stability of the resistivity. In addition, since agglomeration is not easy to occur, the dispersion stability is excellent and screen printing can be performed.

[0034] The dispersion according to one embodiment of the present invention contains copper oxide and contains at least one of copper particles having a shape elongated in one direction, a dendritic shape, or a flat shape.

[0035] According to this configuration, when the copper particles have a shape extending in one direction, a dendritic shape, or a flat shape, it is easy to arrange the particles, and more contacts between the particles can be ensured. At the same time, since the reduced copper oxide particles act as a binder, the mechanical strength and electrical conduction of the conductive pattern are improved, and the time stability of the resistivity is improved. In addition, since agglomeration is not easy to occur, the dispersion stability is excellent, and screen printing can be performed.

[0036] The dispersion according to one embodiment of the present invention preferably includes copper particles having a shape elongated in one direction, a dendritic shape, or a flat shape.

[0037] The dispersion according to one embodiment of the present invention preferably includes at least the copper particles having the dendritic shape.

[0038] In the dispersion according to one embodiment of the present invention, the copper oxide preferably has a particle size of 1 nm to 50 nm.

[0039] In the dispersion according to one embodiment of the present invention, the ratio of the mass of the copper particles to the mass of copper oxide is preferably 1.0 to 7.0.

[0040] In the dispersion according to one embodiment of the present invention, the ratio of the mass of the organic compound to the mass of the copper oxide is preferably 0.0050 or more and 0.30 or less.

[0041] The dispersion according to one embodiment of the present invention preferably contains a reducing agent, and the ratio of the mass of the reducing agent to the mass of the copper oxide is 0.0001 to 0.10.

[0042] The dispersion of one embodiment of the present invention preferably contains a reducing agent, wherein the reducing agent contains at least one selected from the group consisting of hydrazine, hydrazine hydrate, sodium, carbon, potassium iodide, oxalic acid, iron (II) sulfide, sodium thiosulfate, ascorbic acid, tin (II) chloride, diisobutylaluminum hydride, formic acid, sodium hydroborate and sulfite.

[0043] In the dispersion according to one embodiment of the present invention, the copper oxide preferably includes cuprous oxide.

[0044] The dispersion according to one embodiment of the present invention preferably further includes a dispersion medium including at least one selected from the group consisting of terpineol, γ-butyrolactone, cyclohexanone, ethanol, propylene glycol, butanol, propanol, ethylene glycol monoethyl ether acetate, and tetralin.

[0045] The dispersion according to one embodiment of the present invention preferably further includes a dispersion medium, and the dispersion medium includes two or more types.

[0046] A method for producing a structure with a conductive pattern according to one embodiment of the present invention is characterized by comprising the steps of applying the dispersion on a substrate to form a coating film, and irradiating the coating film with laser light to form a conductive pattern on the substrate.

[0047] A method for producing a structure with a conductive pattern according to one embodiment of the present invention is characterized by comprising the steps of applying the dispersion in a desired pattern on a substrate to form a coating film, and firing the coating film to form a conductive pattern on the substrate.

[0048] In the method for producing a structure with a conductive pattern according to one embodiment of the present invention, the firing treatment is preferably performed by generating plasma in an atmosphere containing a reducing gas.

[0049] In the method for producing a structure with a conductive pattern according to one embodiment of the present invention, the firing treatment is preferably performed by a light irradiation method.

[0050] In the method for producing a structure with a conductive pattern according to one embodiment of the present invention, the calcination treatment is preferably performed by heating the coating film at 100° C. or higher.

[0051] In the method for producing a structure with a conductive pattern according to one embodiment of the present invention, it is preferred that the dispersion is applied by an aerosol method to form the desired pattern.

[0052] In the method for producing a structure with a conductive pattern according to one embodiment of the present invention, it is preferred that the dispersion is applied by screen printing.

[0053] In the method for producing a structure with a conductive pattern according to one embodiment of the present invention, it is preferred that after the coating film is formed on a transfer body, the coating film is transferred from the transfer body to the substrate to form the coating film on the substrate.

[0054] The method for manufacturing a structure with a conductive pattern according to one embodiment of the present invention preferably comprises the following steps: after applying the above-mentioned dispersion to a transfer body, bringing the protrusion into contact with the above-mentioned transfer body, removing unnecessary dispersion, and forming a desired pattern on the surface of the above-mentioned transfer body; and bringing the above-mentioned substrate into contact with the surface of the above-mentioned transfer body, thereby transferring the above-mentioned desired pattern to the above-mentioned substrate.

[0055] In the method for producing a structure with a conductive pattern according to one embodiment of the present invention, the conductive pattern is preferably an antenna.

[0056] In the method for producing a structure with a conductive pattern according to one embodiment of the present invention, the conductive pattern is preferably in a mesh shape.

[0057] The method for producing a structure with a conductive pattern according to one embodiment of the present invention preferably further includes a step of forming a solder layer on a portion of the surface of the conductive pattern.

[0058] In the method for producing a structure with a conductive pattern according to one embodiment of the present invention, it is preferred that the electronic component is soldered to the conductive pattern via the solder layer by a reflow method.

[0059] A structure with a conductive pattern according to one embodiment of the present invention is characterized in that it includes a substrate, a layer containing cuprous oxide formed on a surface of the substrate, and a conductive layer formed on a surface of the layer containing cuprous oxide, wherein the conductive layer is a wiring having a line width of 1 μm or more and 1000 μm or less, and the wiring contains reduced copper.

[0060] A structure with a conductive pattern according to one embodiment of the present invention is characterized in that it includes a substrate, a layer containing cuprous oxide formed on a surface of the substrate, and a conductive layer formed on a surface of the layer containing cuprous oxide, wherein the conductive layer is a wiring having a line width of 1 μm or more and 1000 μm or less, and the wiring contains reduced copper, copper, and tin.

[0061] A structure with a conductive pattern according to one embodiment of the present invention is characterized in that it comprises a substrate and a conductive pattern formed on a surface of the substrate, wherein the conductive pattern is a wiring having a line width of 1 μm to 1000 μm, and the wiring contains reduced copper, phosphorus, and voids.

[0062] A structure with a conductive pattern according to one embodiment of the present invention is characterized in that it includes a substrate and a conductive pattern formed on a surface of the substrate, wherein the conductive pattern is a wiring having a line width of 1 μm to 1000 μm, and the wiring contains reduced copper, copper, and tin.

[0063] In the structure with a conductive pattern according to one embodiment of the present invention, the copper preferably has a crystal grain size of 0.1 μm or more and 100 μm or less.

[0064] In the structure with a conductive pattern according to one embodiment of the present invention, the surface roughness of the conductive layer or the conductive pattern is preferably 500 nm or more and 4000 nm or less.

[0065] In the structure with a conductive pattern according to one embodiment of the present invention, it is preferable that the wiring can be used as an antenna.

[0066] In the structure with a conductive pattern according to one embodiment of the present invention, it is preferable that a solder layer is formed on a part of the surface of the conductive layer or the conductive pattern.

[0067] A structure with a conductive pattern according to one embodiment of the present invention is characterized in that it comprises a substrate and a conductive pattern formed on a surface of the substrate, wherein the conductive pattern is a wiring having a line width of not less than 1 μm and not more than 1000 μm, the wiring contains reduced copper, copper oxide and phosphorus, and a resin is arranged in a manner covering the wiring.

[0068] Effects of the Invention

[0069] According to the present invention, a conductive pattern having low resistance and high dispersion stability can be formed on a substrate.

[0070] Furthermore, the present invention can be applied to a screen printing method, and a conductive pattern having excellent temporal stability of resistivity and solderability can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 This is a schematic diagram showing the state of copper oxide and copper particles having a dendritic shape before the dispersion of the third embodiment is applied to a substrate and subjected to a firing treatment.

[0072] Figure 2A to Figure 2D 1 is a schematic cross-sectional view showing a structure with a conductive pattern according to the present embodiment.

[0073] Figure 3 These are explanatory diagrams showing the respective steps in the case of using laser irradiation for firing in the method for producing a structure with a conductive pattern according to the present embodiment.

[0074] Figure 4 These are explanatory diagrams showing the respective steps in the case of using plasma for firing in the method for producing a structure with a conductive pattern according to the present embodiment.

[0075] Figure 5 It is a diagram for explaining the method of forming a coating film using a transfer body according to the present embodiment.

[0076] Fig. 6A , Figure 6B This is a diagram for explaining another example of the method for forming a coating film using a transfer body according to the present embodiment.

[0077] Figure 7 It is a diagram for explaining a method of forming a pattern on a transfer body according to the present embodiment.

[0078] Figure 8 Schematic diagram showing the relationship between copper oxide and phosphate ester salt according to the present embodiment.

[0079] Fig. 9 It is a top view of the structure with a conductive pattern on which a solder layer is formed according to the present embodiment. DETAILED DESCRIPTION

[0080] Hereinafter, an embodiment of the present invention (hereinafter referred to as “the present embodiment”) will be described in detail to illustrate the present invention, but the present invention is not limited to the present embodiment.

[0081] <First Embodiment>

[0082] The dispersion of the first embodiment is characterized in that it contains (1) copper oxide, (2) a dispersant, and (3) a reducing agent. When the dispersion contains the reducing agent, the reduction of copper oxide to copper can be promoted during firing, thereby promoting the sintering of copper.

[0083] The content of the reducing agent satisfies the range of the following formula (1). When the mass ratio of the reducing agent is 0.0001 or more, the dispersion stability is improved and the resistance of the copper film is reduced. In addition, when the mass ratio of the reducing agent is 0.1 or less, the long-term stability of the dispersion is improved.

[0084] 0.0001≦(reducing agent mass / copper oxide mass)≦0.10(1)

[0085] In addition, the content of the dispersant satisfies the range of the following formula (2). This can suppress the aggregation of copper oxide and improve the dispersion stability.

[0086] 0.0050≦(dispersant mass / copper oxide mass)≦0.30(2)

[0087] By limiting the mass range of the reducing agent and the dispersant relative to the copper oxide, the dispersion stability of the dispersion of the first embodiment is improved, and the resistance of the conductive film is effectively reduced. In addition, since plasma, light, or laser can be used for firing treatment, the organic matter in the copper oxide is decomposed, the firing of the copper oxide is promoted, and a conductive film with low resistance can be formed. Therefore, various copper wirings such as electromagnetic wave shielding and circuits can be provided.

[0088] In addition, the dispersion of the first embodiment preferably contains copper particles, and the copper particles have a shape that is elongated in one direction, a dendritic shape, or a flat shape. The dispersion of the first embodiment more preferably contains copper particles having at least a dendritic shape. As a result, copper particles having a specific shape are easily entangled or arranged with each other compared to particles having a small aspect ratio, such as a spherical shape or a regular polyhedron shape. Therefore, more contact points between particles can be ensured, and when the coating film is sintered by a firing treatment, a strong mechanical structure can be formed, and cracks in the resulting conductive film can be suppressed.

[0089] In addition, the dispersion of the first embodiment preferably contains copper particles, and the particle size of the copper particles is preferably 0.1 μm to 100 μm, more preferably 0.5 μm to 50 μm, and particularly preferably 1.0 μm to 10 μm. This has a high effect of suppressing the generation of cracks, and nano-scale copper oxide ultrafine particles enter between copper particles and easily act as a binder. In addition, it is possible to prevent the mechanical strength of the copper particles themselves from being reduced.

[0090] In the dispersion of the first embodiment, the particle size of the copper oxide is preferably 1 nm or more and 50 nm or less. This facilitates sintering, and the copper oxide easily enters between copper particles, so it easily acts as a binder. In addition, the amount of dispersant used can be reduced, and the sintering process can be easily performed.

[0091] In this way, when a coating film formed using a dispersion containing copper particles having a particle size of micrometer order and copper oxide particles of nanometer order is sintered by a firing treatment, the copper particles are bonded to each other to form a strong mechanical structure.

[0092] <Second Embodiment>

[0093] The present inventors have conducted intensive studies and found that, by using a combination of copper oxide particles having a specific particle size and copper particles having a specific particle size in a dispersion and by using a dispersant, both cracks generated during sintering and cracks generated over time can be suppressed, thereby obtaining a conductive film having a low resistivity and excellent temporal stability of the resistivity.

[0094] It is also known that the above dispersion, although containing ultrafine particles at a high concentration, is still difficult to agglomerate. Therefore, it is known that it is also suitable for screen printing and has excellent printability. It is also known that the above dispersion shows excellent dispersion stability with respect to time changes at a high concentration, and can also be screen printed after long-term storage.

[0095] Furthermore, it was found that the dispersion can form a coating film with a relatively thick film thickness by using screen printing, and therefore a large amount of current can be conducted by the obtained conductive film.

[0096] It was also found that the solderability of the conductive film using the dispersion was good.

[0097] The present inventors have completed the present invention based on such a new concept. That is, the dispersion of the second embodiment is characterized in that it contains copper oxide having a particle size of 1 nm to 50 nm, copper particles having a particle size of 0.1 μm to 100 μm, and an organic compound having a phosphate group.

[0098] The particle size here is the average particle size of primary particles of copper oxide particles and copper particles.

[0099] According to the dispersion of the second embodiment, when the coating film formed by the dispersion containing copper particles with a particle size of micrometer level and nanometer level copper oxide particles is sintered by firing treatment, the copper particles are combined with each other to form a strong mechanical structure. In addition, since there are copper oxide particles between the copper particles, they are reduced by firing treatment and changed into metallic copper and sintered at the same time, integrated with the copper particles, and electrical conduction is generated. In other words, the copper oxide particles act as a binder for the copper particles. Therefore, in the obtained conductive film, the rapid deformation during sintering and the generation of cracks due to residual deformation can be suppressed. In addition, a path using copper particles and reduced copper oxide particles as conductors can be formed to reduce resistivity. As a result, a conductive film with low resistivity and high stability of resistivity over time can be obtained.

[0100] In the dispersion of the second embodiment, the upper limit of the particle size of the copper oxide particles is 50 nm. This is because if the particle size is below this upper limit, sintering is easy and the copper oxide particles are easy to enter between the copper particles, so they are easy to function as a binder.

[0101] By making the copper oxide particles have such a size, the melting point peculiar to metal ultrafine particles is lowered, and thus sintering can be performed at a temperature lower than the melting point of the metal to form a conductive film.

[0102] It should be noted that if the particle size of the metal particles is sufficiently small, the proportion of atoms in a high energy state existing on the surface of the particles increases, and the surface diffusion of atoms increases to a level that cannot be ignored. As a result, the interface between the particles is extended due to the surface diffusion, and sintering can be performed at a temperature lower than the melting point of the metal. This phenomenon is called melting point depression.

[0103] On the other hand, the lower limit of the particle size of the copper oxide particles is 1 nm. This is because when the particle size is equal to or larger than this lower limit, the amount of the dispersant used can be reduced, and the calcination process can be easily performed.

[0104] It should be noted that the particle size is determined from the aspects of the compactness and electrical properties of the metallic copper obtained by reducing the copper oxide particles. Furthermore, considering the use of the resin substrate, the firing conditions need to be further lowered from the aspect of reducing the damage to the substrate, so the particle size is preferably smaller. When the primary particle size is 50 nm or less, there is a tendency to reduce the input energy in a manner that does not damage the substrate according to the conditions in the firing treatment described later.

[0105] In the dispersion of the second embodiment, the upper limit of the particle size of the copper particles is 100 μm. This is because when the particle size is below this upper limit, the cracking effect is high and the nano-scale copper oxide ultrafine particles enter between the copper particles and easily act as a binder.

[0106] On the other hand, the lower limit of the average particle size of the copper particles is 0.1 μm. This can prevent the mechanical strength of the copper particles themselves from decreasing.

[0107] In addition, the dispersion of the second embodiment contains relatively large copper particles and a dispersant. As a dispersant, any dispersant can be used without limitation as long as it can disperse copper oxide particles, but an organic compound having a phosphate group is preferred. Therefore, although relatively small copper oxide particles are contained, agglomeration is not easy to occur, and it can be appropriately used in the screen printing method. The agglomerated particles can prevent the supply passage or screen from the ink storage container to the screen in the printing device used in the screen printing method. In addition, since the dispersion of the second embodiment shows excellent dispersion stability to time changes at high concentrations, screen printing can be performed even after long-term storage.

[0108] Screen printing is suitable for forming a conductive film that can flow a large amount of electricity, such as a relatively wide linear pattern of 100 μm, and can form a relatively thick coating film. The dispersion of the second embodiment can be appropriately used in applications that currently use expensive silver ink. In addition, screen printing devices using silver ink are already popular, and since existing screen printing devices can be used, it is easy to replace silver ink with copper ink.

[0109] Furthermore, when the dispersion of the second embodiment is applied to a substrate by screen printing, the coating film becomes fluffy because relatively large copper particles are contained, and as a result, a relatively thick coating film can be formed.

[0110] When a dispersion using copper can be screen-printed to form a coating, a thick coating can be formed as described above, and as a result, a thick conductive film (e.g., 1 μm to 100 μm) can be formed. The conductive substrate having such a thick conductive film has high conductivity and is therefore suitable for use in transparent conductive films, electromagnetic wave shielding, and the like. According to the dispersion of the second embodiment, silver can be replaced with copper, which can significantly reduce the cost of these products.

[0111] In the second embodiment, printing refers to forming a desired pattern (usually including text, images, patterns, etc.) on a medium using ink (one embodiment of the dispersion of the present invention), and is a concept included in coating.

[0112] In the dispersion of the second embodiment, organic components such as the dispersion medium that deteriorate solderability are decomposed by the firing operation, so that the wettability of the solder to the conductive film obtained using the dispersion is improved, making soldering easier.

[0113] In addition, in the dispersion of the second embodiment, the copper particles preferably have a shape elongated in one direction, a dendritic shape, or a flat shape. In addition, the dispersion of the second embodiment more preferably contains copper particles having at least a dendritic shape. As a result, copper particles having a specific shape are easily entangled or arranged with each other compared to particles having a small aspect ratio, such as spherical or regular polyhedral shapes. Therefore, more contact points between particles can be ensured, and when the coating film is sintered by a firing process, a strong mechanical structure can be formed, and cracks in the resulting conductive film can be suppressed.

[0114] In the dispersion of the second embodiment, the mass ratio of the organic compound to the mass ratio of the copper oxide particles is preferably 0.0050 to 0.30. When the organic compound having a phosphate group as a dispersant is within this range, aggregation of copper oxide can be suppressed and dispersion stability can be improved.

[0115] <Third Embodiment>

[0116] The inventors have also conducted intensive studies and have found that by using a dispersion containing copper oxide particles and copper particles having a specific particle shape, both cracks generated during sintering and cracks generated over time can be suppressed, and a conductive film with low resistivity and excellent resistivity stability over time can be obtained.

[0117] It is also known that the above dispersion is difficult to agglomerate despite containing ultrafine particles at a high concentration. Therefore, it is known that it is applicable to screen printing and has excellent printability. It is also known that the above dispersion shows excellent dispersion stability with respect to time changes at a high concentration, and can be screen printed even after long-term storage.

[0118] Furthermore, it was found that the dispersion can form a coating film with a relatively thick film thickness by using screen printing, and therefore a large amount of current can be conducted by the obtained conductive film.

[0119] It was also found that the solderability of the conductive film using the dispersion was good.

[0120] The present inventors have completed the present invention based on such a new viewpoint. That is, the dispersion of the third embodiment is characterized in that it contains copper oxide and contains at least one of copper particles having a shape elongated in one direction, a dendritic shape, or a flat shape (hereinafter also described as copper particles having a specific shape).

[0121] The shape of the particle is a shape that is elongated in one direction and can be explained as follows. First, here, shape refers to the shape of a primary particle. Secondly, let the elongation direction of the particle be the longitudinal direction and the maximum value in the longitudinal direction be the length (L). Let the direction orthogonal to the longitudinal direction be the width direction and the maximum value in the width direction be the width (W). The ratio of the length (L) of the particle to the width (W) is defined as the aspect ratio. A shape with an aspect ratio greater than 1 can be said to be a shape that is elongated in one direction.

[0122] Specifically, the shape extending in one direction includes needle-like, column-like, linear, rope-like, wire-like, rod-like, spindle-like, etc. Here, the difference between needle-like and column-like is not the difference in shape, but is due to the particle size. That is, even if they are the same shape, the one with a larger width (W) is called a column-like, and the one with a smaller width (W) is called a needle-like.

[0123] The shape elongated in one direction is not limited to the case where the cross-sectional dimensions along the elongation direction of the particle are constant, and there may be a part that is larger or smaller than other parts. In this case, the width (W) refers to the diameter of the bottom surface of the cylinder when the particle is regarded as a cylinder of equal volume.

[0124] The shape of the cross section of the particle is not particularly limited, and may be a circle, a triangle, a quadrilateral, a polygonal shape or a shape formed by connecting curved lines or straight lines.

[0125] In addition, the particle is not limited to a shape extending straight in the extension direction, and may be a shape extending in a curved manner. In this case, the shape of the particle is called hair-like, thread-like, rope-like, wire-like, etc.

[0126] When the shape of the particles is elongated in one direction, the particles are easily arranged and a large number of contact points between the particles can be ensured. From this point of view, the aspect ratio of the particles is preferably 3 or more.

[0127] In the third embodiment, the dendritic shape can be described as follows. First, the shape here refers to the shape of the primary particle. Secondly, the dendritic shape is composed of a trunk having the shape extending in one direction and at least one branch branching from the trunk. This shape is also called a dendrite.

[0128] When the shape of the particles is a dendritic shape, the particles are easy to arrange and more contact points between the particles can be ensured. In addition, when the shape of the particles is a dendritic shape, the particles can be three-dimensionally entangled with each other. From these aspects, the aspect ratio of the trunk of the particles is preferably 3 or more. In addition, the number of branches is not particularly limited, preferably 2 or more, particularly preferably 3 or more. It should be noted that the aspect ratio of the trunk is the same as that described in the above-mentioned particles having a shape extending in one direction.

[0129] In addition, in the third embodiment, the flat shape can be described as follows. First, the shape here refers to the shape of the primary particle. Secondly, the flat shape refers to the shape of the main surface having a plane or a curved surface. Let the maximum length (a) of the main surface be vertical, and let the maximum length (b) orthogonal to the length (a) be horizontal. The ratio of the vertical (a) length of the main surface of the particle to the thickness (c) is defined as the aspect ratio. A shape with an aspect ratio greater than 3 can be said to be flat.

[0130] Specifically, the flat shape includes plate-like, leaf-like, scale-like (also called flake-like), etc. Here, the difference between plate-like, leaf-like, and scale-like is not the difference in shape, but is due to the particle size. That is, even if they are the same shape, the one with a thicker thickness (c) is called plate-like, the thinner one is called leaf-like, and the thinner one is called scale-like.

[0131] When the particle shape is flat, the particles are easily arranged and a large number of contact points between particles can be ensured. From this point of view, the aspect ratio of the particle is preferably 5 or more.

[0132] The dispersion according to the third embodiment more preferably contains at least copper particles having a dendritic shape.

[0133] According to the dispersion of the third embodiment, copper particles having a specific shape are more likely to be entangled or arranged with each other than particles having a small aspect ratio such as spheres or regular polyhedrons, so that more contact points between the particles can be ensured.

[0134] Therefore, when the coating is sintered by a firing process, a strong mechanical structure can be formed. In addition, since copper oxide particles are present between the copper particles, they are reduced by the firing process and changed into metallic copper and sintered at the same time, integrated with the copper particles, and electrical conduction is generated. In other words, the copper oxide particles act as an adhesive for the copper particles. Therefore, in the resulting conductive film, rapid deformation during sintering and cracks caused by residual deformation can be suppressed. In addition, a path using copper particles and reduced copper oxide particles as conductors can be formed, which can reduce resistivity. As a result, a conductive film with low resistivity and high time stability of resistivity can be obtained.

[0135] The dispersion of the third embodiment contains copper particles having a specific shape. Therefore, the dispersion is not easily agglomerated and can be appropriately used in the screen printing method. It is possible to prevent the agglomerated particles from clogging the supply path from the ink storage container to the screen or the screen in the printing device used in the screen printing method.

[0136] The dispersion of the third embodiment can be suitably used in applications that currently use expensive silver ink. In addition, screen printing devices that use silver ink are already widespread, and since existing screen printing devices can be used, it is easy to switch from silver ink to copper ink.

[0137] Furthermore, when the dispersion of the third embodiment is applied to a substrate by screen printing, the coating film becomes bulky because the dispersion contains copper particles having a specific shape, and as a result, a coating film having a relatively thick film thickness can be formed.

[0138] A conductive substrate having such a thick conductive film has high conductivity and is therefore suitable for use in transparent conductive films, electromagnetic wave shielding, etc. According to the dispersion of the third embodiment, silver can be replaced with copper, and the cost of these products can be significantly reduced.

[0139] In addition, the dispersion of the third embodiment contains copper particles having a specific shape, so it is not easy to aggregate, and exhibits excellent dispersion stability with respect to changes over time at a high concentration. Therefore, screen printing can be performed even after long-term storage.

[0140] In the dispersion of the third embodiment, organic components such as the dispersion medium that deteriorate solderability are decomposed by the firing operation, so that the wettability of the solder to the conductive film obtained using the dispersion is improved, making soldering easier.

[0141] In particular, when the dispersion of the third embodiment contains copper particles having a dendritic shape, the above-mentioned effect is enhanced, which is the most preferable.

[0142] Figure 1 Schematic diagram showing the state of copper oxide and copper particles having a dendritic shape before the dispersion of the third embodiment is applied to a substrate and fired. Figure 1 As shown, in the coating film 1 before firing, a plurality of copper particles 5 having a dendritic shape are entangled or arranged with each other. Therefore, the copper particles 5 are in contact with each other at a plurality of contact points X. In addition, the copper oxide particles 2 having a small particle size enter between these copper particles 5 .

[0143] Since the copper particles 5 having a dendritic shape are in contact with each other through the branches 5b branching from the trunk 5a, the number of contact points X increases compared to copper particles having no branches and a shape extending in one direction. As a result, the copper particles 5 are more easily dispersed and less likely to aggregate in the dispersion and the coating film 1. As a result, the above-mentioned effects can be more significantly exerted.

[0144] In the dispersion of the third embodiment, the particle size of the copper particles is preferably 0.1 μm to 100 μm, more preferably 0.5 μm to 50 μm, and particularly preferably 1.0 μm to 10 μm. This has a high effect of suppressing the generation of cracks, and the nano-scale copper oxide ultrafine particles enter between the copper particles and easily act as a binder. It is also possible to prevent the mechanical strength of the copper particles themselves from being reduced.

[0145] In the dispersion of the third embodiment, the particle size of the copper oxide is preferably 1 nm or more and 50 nm or less. This facilitates sintering, and the copper oxide easily enters between copper particles, so it easily acts as a binder. In addition, the amount of dispersant used can be reduced, and the sintering process can be easily performed.

[0146] In this way, when a coating film formed using a dispersion containing copper particles having a particle size of micrometer order and copper oxide particles of nanometer order is sintered by a firing treatment, the copper particles are bonded to each other to form a strong mechanical structure.

[0147] <Other methods>

[0148] In addition, in the dispersions of the second and third embodiments, the ratio of the mass of the copper particles to the mass of the copper oxide particles is preferably 0.5 or more and 10 or less. In addition, the ratio of the mass of the copper particles to the mass of the copper oxide particles is more preferably 1.0 or more and 7.0 or less. In addition, the ratio of the mass of the copper particles to the mass of the copper oxide particles is further preferably 1.5 or more and 6.0 or less. When the mass ratio of the copper particles is within this range, there is a large amount of copper oxide, so the copper particles obtained by reduction are sufficiently bonded to each other. Therefore, the mechanical strength of the conductive film after firing is improved. In addition, the crack suppression effect brought about by the copper particles obtained by reduction can be fully exerted.

[0149] In addition, the dispersion of the second and third embodiments described above preferably contains a reducing agent, and the ratio of the mass of the reducing agent to the mass of the copper oxide is preferably 0.0001 or more and 0.10 or less. By specifying the mass ratio of the reducing agent, the dispersion stability is improved, the resistance of the copper film is reduced, and the long-term stability of the dispersion is improved. In addition, the effect of suppressing the generation of cracks is high, and the nano-scale copper oxide ultrafine particles enter between the copper particles and easily act as a binder. And it is possible to prevent the mechanical strength of the copper particles themselves from being reduced. Since relatively large copper particles are contained and an organic compound having a phosphate group is contained as a dispersant, it is not easy to agglomerate even if relatively small copper oxide particles are contained.

[0150] In the first to third embodiments, a reducing agent is preferably included, and the reducing agent is at least one selected from the group consisting of hydrazine, hydrazine hydrate, sodium, carbon, potassium iodide, oxalic acid, iron (II) sulfide, sodium thiosulfate, ascorbic acid, tin (II) chloride, diisobutylaluminum hydride, formic acid, sodium borohydride, and sulfite. This improves the dispersion stability of copper oxide and reduces the resistance of the conductive film.

[0151] In addition, the reducing agent is particularly preferably hydrazine or hydrazine hydrate. By using hydrazine or hydrazine hydrate as a reducing agent for the dispersion, the dispersion stability of copper oxide is further improved, and it helps to reduce copper oxide during firing, and the resistance of the conductive film is further reduced. In addition, in reverse printing, the drying speed of the dispersion can be controlled. In addition, copper wires with high precision (for example, 0.1 to 5 μm) line width can be formed, and copper wires with a line width of less than 5 μm in particular will not be seen by the human eye, and are therefore suitable as transparent conductive films.

[0152] In the first to third embodiments, the copper oxide is preferably cuprous oxide. This facilitates reduction of the copper oxide and allows easy sintering of the copper produced by the reduction.

[0153] In the first to third embodiments, it is preferred that a dispersion medium is further included, and the dispersion medium is at least one selected from the group consisting of terpineol, γ-butyrolactone, cyclohexanone, ethanol, propylene glycol, butanol, propanol, ethylene glycol monoethyl ether acetate, and tetralin. These dispersion media may have a reducing effect, but when the above-mentioned reducing agent is included in the dispersion, the function as a dispersion medium is exerted.

[0154] In the first to third embodiments, it is preferred that a dispersion medium is further included, and two or more dispersion media are included.

[0155] <Structure with Conductive Pattern>

[0156] The structure with a conductive pattern is characterized in that it has a substrate and a conductive pattern formed on the surface of the substrate, wherein the conductive pattern is a wiring with a line width of 1 μm or more and 1000 μm or less, and contains reduced copper, phosphorus and voids. With this structure, as described below, a wiring with a good shape can be formed on a substrate of a desired shape.

[0157] The structure with a conductive pattern is characterized in that it includes a substrate and a conductive pattern formed on a surface of the substrate, the conductive pattern is a wiring with a line width of 1 μm or more and 1000 μm or less, and the wiring contains reduced copper, copper and tin.

[0158] In addition, the structure with a conductive pattern is characterized in that it includes a substrate, a layer containing cuprous oxide formed on the surface of the substrate, and a conductive layer formed on the surface of the layer containing cuprous oxide, the conductive layer is a wiring with a line width of 1 μm or more and 1000 μm or less, and the wiring contains reduced copper.

[0159] In addition, the structure with a conductive pattern is characterized in that it has a substrate, a layer containing cuprous oxide formed on the surface of the substrate, and a conductive layer formed on the surface of the layer containing cuprous oxide, the conductive layer is a wiring with a line width of 1 μm or more and 1000 μm or less, and the wiring contains reduced copper, copper and tin. The layer containing cuprous oxide is a layer in which the ratio of copper to oxygen Cu / O is 0.5 or more and 3.0 or less. By analyzing the cross section of the structure with a conductive pattern by an EDX method, the Cu / O in the layer containing cuprous oxide can be quantified.

[0160] In the structure with a conductive pattern, the wiring can preferably be used as an antenna. With this configuration, an antenna with a good shape can be formed.

[0161] In the structure with a conductive pattern, a solder layer is preferably formed on a portion of the surface of the conductive layer or the conductive pattern. Since the conductive pattern is formed by firing the copper oxide of the above-mentioned dispersion, the organic binder is decomposed during the firing process. Therefore, in the conductive pattern, the wettability of the solder is high and the solder layer can be easily formed, thereby making it easier to solder electronic components in the conductive pattern compared to a conductive pattern formed without using the above-mentioned dispersion.

[0162] In addition, the structure with a conductive pattern is characterized in that it has a substrate and a conductive pattern formed on the surface of the substrate, the conductive pattern is a wiring with a line width of more than 1μm and less than 1000μm, contains reduced copper, copper oxide and phosphorus, and is configured with resin in a manner to cover the wiring.

[0163] (Configuration of Structure with Conductive Pattern)

[0164] When the dispersions of the first to third embodiments are used, two types of structures with conductive patterns can be obtained by firing. FIG2 is a schematic cross-sectional view of the structure with a conductive pattern of this embodiment. The above dispersion is used to form a coating film on a substrate, and the copper oxide particles of the dispersion are fired by laser irradiation, thereby obtaining Figure 2A The desired pattern is printed on the substrate using the dispersion and fired using plasma to obtain a structure with a conductive pattern. Figure 2B A structure with a conductive pattern.

[0165] like Figure 2AAs shown, the structure 10 with a conductive pattern may include a substrate 11 and a surface layer 14, wherein the surface layer 14 is formed by arranging an insulating region 12 and a conductive pattern region 13 adjacent to each other, wherein the insulating region 12 is a region containing copper oxide and phosphorus-containing organic matter when observed in cross section on the surface formed by the substrate 11, and the conductive pattern region 13 contains reduced copper obtained by reducing copper oxide by firing. The conductive pattern region 13 contains phosphorus elements derived from phosphorus-containing organic matter as a dispersant. The conductive pattern region 13 is formed by firing copper oxide ink as a dispersion, so that during the firing process, the organic binder contained in the dispersion is decomposed, and the wettability of the solder in the obtained conductive pattern region 13 is improved. As a result, compared with a conductive pattern formed without using a dispersion, the surface of the conductive pattern region 13 can easily form a solder layer described later, and the soldering of electronic components is easy.

[0166] like Figure 2B As shown, the structure 10 with a conductive pattern may include a substrate 11 and a conductive pattern region 13 containing reduced copper when viewed in cross section on a surface formed by the substrate 11. Phosphorus is contained in the conductive pattern region 13. In the conductive pattern region 13, the organic binder contained in the dispersion is effectively decomposed in the process of firing the dispersion, so that the wettability of the solder is effectively improved in the conductive pattern region 13. As a result, a solder layer can be more easily formed on the surface of the conductive pattern region 13.

[0167] In addition, the conductive pattern region 13 may contain a portion of copper oxide particles that are not reduced in the firing process, such as cuprous oxide. The conductive pattern region 13 may contain copper obtained by firing the copper particles of the dispersion of the second and third embodiments, and may also contain tin. In addition, voids may be included in the insulating region 12 and the conductive pattern region 13. By providing the conductive pattern region 13 with voids (empty walls), solder enters there, and the adhesion between the conductive pattern region 13 and the solder layer is improved. In addition, solder refers to a metal containing tin.

[0168] In addition, the surface layer 14 does not necessarily have to be homogeneous as a whole, and may have differences in electrical conductivity, particle state (fired and unfired), etc., as in the relationship between the insulating region 12 and the conductive pattern region 13, and may have a boundary (interface) between the two.

[0169] In this case, for example Figure 2CAs shown, in the conductive layer 18, a layer 17 containing cuprous oxide may be formed on the surface of the substrate 11, and the layer contains, for example, cuprous oxide, which is copper oxide particles that are not reduced in the firing process. The conductive layer 18 containing reduced copper obtained by reducing the copper oxide particles is formed on the surface of the layer 17 containing cuprous oxide. In this way, by forming the layer 17 containing cuprous oxide, the adhesion between the substrate 11 and the conductive layer 18 is improved, which is preferred. From the aspect of the adhesion between the substrate 11 and the conductive layer 18, the layer thickness of the layer 17 containing cuprous oxide is preferably 0.005 μm to 8 μm, more preferably 0.05 μm to 5 μm, further more preferably 0.1 μm to 3 μm, and particularly preferably 0.2 μm to 1 μm.

[0170] In addition, if Figure 2D As shown, the conductive layer 18 may contain reduced copper (Cu) obtained by reducing copper oxide particles, and copper (Cu) obtained by sintering the copper particles of the dispersion of the second and third embodiments. P ). In addition, the conductive layer 18 may include voids. By providing the conductive layer 18 with voids, tin (Sn) contained in the solder enters the voids. As a result, the adhesion between the conductive layer 18 and the solder layer is improved. In addition, by providing the conductive layer 18 with copper (Cu P ) has reduced copper (Cu) around it, and the adhesion between the conductive layer 18 and tin (Sn) is further increased. The particle size of the reduced copper (Cu) at this time is preferably 5 to 20 nm.

[0171] In addition, the grain size of copper contained in the conductive pattern area 13 and the conductive layer 18 is preferably 0.1 μm to 100 μm, more preferably 0.5 μm to 50 μm, and particularly preferably 1.0 μm to 10 μm. Here, the grain size refers to the size of the metal after firing. As a result, the adhesion between the conductive pattern area 13 and the conductive layer 18 and the solder layer is improved.

[0172] In addition, the surface roughness of the conductive pattern region 13 and the conductive layer 18 is preferably 500 nm to 4000 nm, more preferably 750 nm to 3000 nm, and even more preferably 1000 nm to 2000 nm. Thus, the solder layer is easily attached to the conductive pattern region 13 and the conductive layer 18, and the adhesion between the conductive pattern region 13 and the conductive layer 18 and the solder layer is improved.

[0173] By forming the conductive pattern area 13 or the conductive layer 18 as shown in FIG. 2 , a wiring with a line width of 0.1 μm to 1 cm can be drawn, which can be used as a copper wiring or an antenna. By effectively utilizing the characteristics of the nanoparticles of the copper oxide particles contained in the above-mentioned dispersion, the line width of the conductive pattern area 13 or the conductive layer 18 is more preferably 0.5 μm to 10000 μm, further preferably 1 μm to 1000 μm, further preferably 1 μm to 500 μm, further preferably 1 μm to 100 μm, and particularly preferably 1 μm to 5 μm. When the line width is 5 μm or less, the conductive pattern area 13 or the conductive layer 18 as a wiring cannot be visually recognized, so it is preferred from the perspective of aesthetics.

[0174] The conductive pattern may be formed in a mesh shape. The mesh shape refers to lattice-shaped wiring, which improves transmittance and makes it transparent, and is therefore preferred.

[0175] The substrate used in this embodiment is a substrate having a surface on which a coating film is formed, and it may have a plate shape or may be a three-dimensional object. In this embodiment, a conductive pattern may also be formed on a surface including a curved surface or a step formed by a three-dimensional object. The substrate in this embodiment refers to a substrate material of a circuit substrate sheet for forming a wiring pattern, or a housing material of a housing with wiring, etc.

[0176] In addition, a light-transmissive resin layer (not shown) can be provided in a manner covering the surface layer 14 or the conductive pattern area 13. In the method for manufacturing the structure 10 with a conductive pattern described later, the resin layer can prevent the coating from coming into contact with oxygen during light irradiation, thereby promoting the reduction of copper oxide. As a result, it is not necessary to provide an oxygen-free or low-oxygen atmosphere around the coating, such as equipment for forming a vacuum atmosphere or an inert gas atmosphere, during light irradiation, thereby reducing manufacturing costs. In addition, the resin layer can prevent the conductive pattern area 13 from peeling off or scattering due to the effects of heat from light irradiation, etc. As a result, the structure 10 with a conductive pattern can be manufactured with a high yield.

[0177] <Method for producing a structure with a conductive pattern>

[0178] The method for producing a structure with a conductive pattern is characterized in that it comprises a step of applying the above-mentioned dispersion on a substrate to form a coating film, and a step of irradiating the coating film with laser to form a conductive pattern on the substrate. By firing by laser irradiation, the copper particles of the dispersion can be fired and the conductive pattern can be formed at one time.

[0179] The method for producing a structure with a conductive pattern comprises the steps of applying the dispersion in a desired pattern on a substrate to form a coating film, and firing the coating film to form a conductive pattern on the substrate.

[0180] In this case, the calcination treatment is preferably performed by generating plasma in an atmosphere containing a reducing gas. In addition, the calcination treatment is preferably performed by a light irradiation method. In addition, the calcination treatment is preferably performed by heating the coating film with heat of 100° C. or higher.

[0181] [Conductive film (conductive pattern) formation method]

[0182] In the method for forming a conductive film of the present embodiment, the copper oxide in the coating is reduced to generate copper, and a conductive film (copper film) is formed by its own welding and the welding and integration with the copper particles added to the copper oxide ink as a dispersion. This process is called firing. Therefore, there is no particular limitation as long as the method can form a conductive film based on the reduction and welding of copper oxide and the integration with copper particles. The firing in the method for forming a conductive film of the present embodiment can be carried out, for example, using a firing furnace, or using plasma, infrared rays, flash lamps, lasers, etc. alone or in combination. After firing, a solder layer described later can be formed on a part of the conductive film.

[0183] Reference Figure 3 The method for producing a structure with a conductive pattern when laser irradiation is used for firing in the present embodiment will be described in more detail. Figure 3 1 is an explanatory diagram showing each step in the case where laser irradiation is used in firing in the method for producing a structure with a conductive pattern according to the present embodiment. Figure 3 In (a), copper acetate is dissolved in a mixed solvent of water and propylene glycol (PG), and hydrazine is added and stirred.

[0184] Then, in Figure 3 In (b) and (c), the supernatant and the precipitate are separated by centrifugation. Figure 3 In step (d), a dispersant and alcohol are added to the obtained precipitate to disperse it.

[0185] Next, in Figure 3 In (e) and (f), concentration and dilution are repeated using a UF membrane module to perform solvent replacement, thereby obtaining a dispersion I (copper oxide ink) containing copper oxide.

[0186] exist Figure 3 In (g) and (h), the dispersion I is applied by spraying on a substrate ( Figure 3(h) is described as "PET"), forming a coating layer (coating film) containing copper oxide and a phosphorus-containing organic substance ( Figure 3 (h) is recorded as "Cu2O").

[0187] Then, in Figure 3 In (i), the coating layer is irradiated with a laser, for example, to selectively sinter a portion of the coating layer to reduce the copper oxide to copper ( Figure 3 (i) is recorded as "Cu"). As a result, Figure 3 In (j), a structure with a conductive pattern having a surface layer formed on a substrate is obtained, wherein the surface layer is an insulating region including copper oxide and a phosphorus-containing organic substance ( Figure 3 (j) is represented by "A") and a conductive film (conductive pattern) region containing copper and phosphorus elements ( Figure 3 (j) is described as "B") and is arranged adjacent to each other. The conductive pattern region can be used as wiring.

[0188] In addition, the conductive pattern region may contain, for example, cuprous oxide, which is copper oxide particles that are not reduced in the firing process. The insulating region and the conductive pattern region may contain copper obtained by firing the copper particles of the dispersion of the second and third embodiments, and may also contain tin. In addition, the insulating region and the conductive pattern region may contain voids. By providing the conductive pattern region with voids, solder enters there, and the adhesion between the conductive pattern region and the solder layer is improved.

[0189] In addition, the surface layer does not mean that the entire surface is homogeneous, and there may be differences in electrical conductivity, particle state (fired and unfired), etc., such as the relationship between the insulating region and the conductive pattern region, and there may be a boundary (interface) between the two. By forming a layer of unreduced copper oxide between the substrate and the surface layer, the adhesion between the substrate and the surface layer is improved, which is preferred.

[0190] Thus, by firing by laser irradiation, the copper particles of the dispersion can be fired and the conductive pattern region can be formed at one time. In addition, the organic binder contained in the dispersion is decomposed by firing the copper particles, so the wettability of the solder of the obtained conductive pattern is improved.

[0191] Next, refer to Figure 4 The method for producing a structure with a conductive pattern in the case of using plasma for firing in the present embodiment will be described in more detail. Figure 4 1 is an explanatory diagram showing each step in the case where plasma is used in firing in the method for producing a structure with a conductive pattern according to the present embodiment. Figure 4 The steps (a) to (f) in Figure 3 same.

[0192] Figure 4 In (g) and (k), the dispersion I is printed in a desired pattern on a substrate made of, for example, PET by, for example, inkjet printing, to form a coating layer ( Figure 4 (k) is recorded as "Cu2O").

[0193] then, Figure 4 In (k), the coating layer is irradiated with plasma, for example, and the coating layer is fired to reduce the copper oxide to copper. As a result, Figure 4 In (l), a conductive pattern region ( Figure 4 (l) is a conductive substrate recorded as "B").

[0194] Thus, by firing by plasma irradiation, the copper particles of the dispersion printed in a desired pattern by inkjet printing etc. can be fired. In addition, since the organic binder contained in the dispersion is effectively decomposed, the wettability of the solder in the obtained conductive pattern is effectively improved.

[0195] (Method for forming a coating film on a substrate using a dispersion)

[0196] In addition, in the method for manufacturing a structure with a conductive pattern, the formation of the desired pattern is preferably carried out by applying the dispersion using an aerosol method, and is also preferably carried out by applying the dispersion by screen printing. The viscosity and flow properties of the dispersions of the first to third embodiments are suitable for screen printing, and thus can be appropriately used for screen printing.

[0197] In the method for producing a structure with a conductive pattern, it is preferred that after forming a coating film on a transfer body, the coating film is transferred from the transfer body to a substrate to form a coating film on the substrate.

[0198] Figure 5 Fig. 6 is a diagram for explaining another example of the method for forming a coating film using a transfer body according to the present embodiment.

[0199] like Figure 5 As shown, the dispersion 31 is transferred to the transfer body 30 in a desired pattern. After that, a cylindrical substrate 40 (circular in cross section) is placed on the surface of the transfer body 30 to which the dispersion 31 is transferred, and then a pressing plate 50 is placed on the substrate 40. The substrate 40 is rotated on the transfer body 30 while being pressed against the transfer body 30 by the pressing plate 50. Thus, the dispersion 31 of the transfer body 30 is transferred to the substrate 40.

[0200] Thus, when the substrate 40 is pressed against the surface of the transfer body 30 to which the dispersion 31 is transferred, the transfer body 30 makes line contact with the substrate 40. Therefore, fine printing can be performed not only when the printing surface of the substrate 40 is flat, but also when it is a curved surface or the printing surface has undulations.

[0201] In addition, if Fig. 6A As shown, the dispersion 31 is transferred to the transfer body 30 in a desired pattern. Then, while the transfer body 30 is pressed against the substrate 40, the transfer body 30 is relatively moved relative to the substrate 40 in the printing direction, thereby Figure 6B As shown in FIG. 1 , the dispersion 31 of the transfer body 30 can be transferred to the substrate 40. The transfer body 30 can be as follows. Figure 5 Although it is plate-shaped as shown, it may have a curved surface as shown in Fig. 6. Thus, since the dispersion 31 is transferred from the transfer body 30 to the substrate 40 by a predetermined pressing force, good printing can be performed even when the printing surface of the substrate 40 is curved.

[0202] In addition, the formation of a desired pattern in the manufacturing method of a structure with a conductive pattern is preferably characterized in that it has the following steps: after applying the dispersion to the transfer body, bringing the protrusion into contact with the transfer body, removing unnecessary dispersion, and forming the desired pattern on the surface of the transfer body; and bringing the substrate into contact with the surface of the transfer body to transfer the desired pattern to the substrate.

[0203] use Figure 7 A method for forming a desired pattern on a transfer body will be described. Figure 7 It is a diagram for explaining a method of forming a pattern on a transfer body according to the present embodiment.

[0204] like Figure 7 As shown in FIG. 1 , for example, by bringing the convex portion 60 of the mold into contact with the dispersion 31 applied on the surface of the transfer body 30, the dispersion in the portion where the convex portion 60 contacts is removed from the surface of the transfer body 30. Thus, a desired pattern of the dispersion 31 is formed on the surface of the transfer body 30. Thereafter, by bringing the transfer body 30 formed with the desired pattern into contact with the substrate 40, the desired pattern can be transferred to the substrate 40 (see FIG. 1 ). Figure 3 and Figure 6B ) The method for applying the dispersion 31 to the surface of the transfer body 30 is not particularly limited as long as the dispersion 31 can be uniformly applied to the surface of the transfer body 30 .

[0205] In the structure with a conductive pattern, the conductive pattern is preferably an antenna. In addition, the conductive pattern may be formed in a mesh shape. In addition, the conductive pattern preferably has a line width of 1 μm or more and 1000 μm or less.

[0206] In addition, the method for manufacturing a structure with a conductive pattern preferably further includes a step of forming a solder layer on a portion of the surface of the conductive pattern. In the copper firing step, the organic binder contained in the coating film is decomposed, so that the wettability of the solder on the surface of the obtained conductive pattern is improved, and the solder layer can be easily formed.

[0207] In the method for producing a structure with a conductive pattern, it is preferred that the electronic component is soldered to the conductive pattern via the solder layer by a reflow method.

[0208] In the method for producing a structure with a conductive pattern, a material with low heat resistance can be used for the structure by performing a firing treatment using a plasma firing method or a light irradiation method in which plasma is generated in an atmosphere containing a reducing gas.

[0209] In addition, in the method for manufacturing a structure with a conductive pattern, by performing a firing treatment, not only the reduction of copper oxide and the firing of copper particles are performed, but also the organic matter contained in the dispersion is decomposed, thereby preventing the increase of resistivity, and removing the organic matter and the oxide film from the surface of the conductive film, thereby improving the weldability. By performing the firing treatment, the organic components such as the dispersion medium that deteriorate the weldability are decomposed, so the wettability of the solder to the conductive film is improved, and welding becomes easy. Thus, a structure with a conductive pattern having a conductive film with excellent weldability can be obtained. In the decomposition of the organic components of the conductive film, the firing treatment that generates plasma in an atmosphere containing a reducing gas is particularly preferred.

[0210] Next, the constituent elements of the dispersions according to the first to third embodiments will be described in further detail.

[0211] [Dispersion]

[0212] Next, use Figure 8 The states of copper oxide and a dispersant in the copper oxide ink as a dispersion will be described. Figure 8 Schematic diagram showing the relationship between copper oxide and phosphate ester salt according to the present embodiment.

[0213] like Figure 8 As shown, in the dispersion 1, a phosphate ester salt 3 as a dispersant, which is an example of a phosphorus-containing organic substance, surrounds a copper oxide 2 as an example of copper oxide in such a manner that phosphorus 3a faces inward and ester salt 3b faces outward. Since the phosphate ester salt 3 exhibits electrical insulation, it hinders electrical conduction between adjacent copper oxides 2. In addition, the phosphate ester salt 3 suppresses aggregation of the dispersion 1 by a steric hindrance effect.

[0214] Therefore, although the copper oxide 2 is a semiconductor and is conductive, since it is covered with the phosphate ester salt 3 showing electrical insulation, the dispersion 1 shows electrical insulation, and in cross-sectional observation (the cross-sectional view along the up and down direction shown in FIG. 2 ), insulation between adjacent conductive pattern areas (described later) on both sides of the dispersion 1 can be ensured.

[0215] On the other hand, in the conductive pattern region, a portion of the coating film containing copper oxide and phosphorus-containing organic matter is irradiated with light, and the copper oxide is reduced to copper in the portion. Copper obtained by reducing copper oxide in this way is called reduced copper. In addition, in the portion, the phosphorus-containing organic matter is modified to phosphorus oxide. Among phosphorus oxides, organic matter such as the above-mentioned ester salt 3b is decomposed by heat such as laser light and does not show electrical insulation.

[0216] In addition, if Figure 8 As shown, when copper oxide 2 is used, the copper oxide is transformed into reduced copper and sintered by heat from laser or the like, and adjacent copper oxides 2 are integrated with each other. Thus, a region having excellent electrical conductivity (hereinafter referred to as a "conductive pattern region") can be formed.

[0217] In the conductive pattern region, phosphorus element remains in the reduced copper. The phosphorus element exists in the form of at least one of phosphorus element alone, phosphorus oxide, and phosphorus-containing organic matter. Such residual phosphorus element segregates and exists in the conductive pattern region, which may increase the resistance of the conductive pattern region.

[0218] [Copper oxide]

[0219] In the present embodiment, copper oxide is used as one of the metal oxide components. As copper oxide, cuprous oxide (Cu2O) is preferred. This is because it is also easy to reduce among metal oxides, and it is easy to sinter by using microparticles. In terms of price, since it is copper, the cost is lower than that of precious metals such as silver, which is beneficial to migration.

[0220] The dispersion of the present embodiment contains copper oxide particles having an average secondary particle size of 1 nm to 500 nm.

[0221] The average secondary particle size of copper oxide is not particularly limited, but is preferably 500 nm or less, more preferably 200 nm or less, and further preferably 80 nm or less. The average secondary particle size of copper oxide is preferably 1 nm or more, more preferably 5 nm or more, further preferably 10 nm or more, and particularly preferably 15 nm or more. Here, the average secondary particle size refers to the average particle size of agglomerates (secondary particles) formed by the aggregation of a plurality of primary particles.

[0222] When the average secondary particle size is 500 nm or less, it is preferred because a fine pattern tends to be easily formed on the substrate. When the average secondary particle size is 1 nm or more, the long-term storage stability of the copper oxide ink as a dispersion is improved, which is preferred. The average secondary particle size of copper oxide can be measured by the accumulation method using, for example, FPAR-1000 manufactured by Otsuka Electronics.

[0223] In addition, about the preferred range of the average primary particle size of cupric oxide, from the aspect of the compactness and electrical properties of the metal obtained by reducing it, further, considering the use of resin substrates, from the aspect of reducing the damage to the substrate, the firing conditions need to be further low-temperature. Therefore, the preferred average primary particle size is less than 100nm, more preferably less than 50nm, and more preferably less than 20nm. When the average primary particle size is less than 100nm, in the firing treatment described later, the input energy can be reduced in a manner that does not damage the substrate. The lower limit of the average primary particle size of cuprous oxide is not particularly limited, and for the sake of ease of handling, it is preferably more than 1nm, more preferably more than 5nm. Thus, the situation that the amount of dispersant is increased to ensure dispersion stability due to the small particle size can be suppressed, so the firing treatment becomes easy. The average primary particle size can be measured using a transmission electron microscope or a scanning electron microscope. The average primary particle size can be measured using, for example, a transmission electron microscope or a scanning electron microscope.

[0224] The copper oxide in the dispersion is easily reduced by plasma treatment, heat treatment at 100°C or above, or light treatment to become metal, and conductivity is obtained by sintering it, and it acts as a binder to integrate the copper particles further added, thereby contributing to low resistance and improved strength. It should be noted that in this embodiment, the average particle size of the cuprous oxide particles does not affect the crack prevention effect of the copper particles having a metal wire shape, a dendrite shape, and a scale shape described later.

[0225] Cuprous oxide may be a commercial product or may be synthesized. Commercial products include those manufactured by Rare Metal Materials Research Institute (KK) having an average primary particle size of 5 to 50 nm. The following method may be used as a synthesis method.

[0226] (1) A method for heat reduction, in which water and acetylacetonate copper complex are added to a polyol solvent, the organic copper compound is temporarily heated to dissolve, and then water required for the reaction is added, the temperature is further increased, and heating is performed at the reduction temperature of the organic copper.

[0227] (2) A method in which an organic copper compound (copper-N-nitrosophenylhydroxylamine complex) is heated at a high temperature of about 300° C. in an inert atmosphere in the presence of a protective material such as hexadecylamine.

[0228] (3) A method of reducing a copper salt dissolved in an aqueous solution with hydrazine.

[0229] Among them, the method (3) is preferred because the operation is simple and cuprous oxide having a small average particle size can be obtained.

[0230] Since the obtained cuprous oxide is a soft aggregate, a copper oxide dispersion dispersed in a dispersion medium is prepared for printing and coating. After the synthesis is completed, the synthetic solution and the cuprous oxide are separated by known methods such as centrifugal separation. In addition, the obtained cuprous oxide is added to the dispersant and dispersion medium described later, and stirred and dispersed by known methods such as a homogenizer. Sometimes there is a situation where it is difficult to disperse or insufficiently dispersed using a dispersion medium. As an example of such a situation, after dispersion using a dispersion medium such as butanol that is easily dispersed, it is replaced with a desired dispersion medium and concentrated to a desired concentration. As an example of a method, a method of repeatedly concentrating using a UF membrane, diluting using a desired dispersion medium, and concentrating can be cited. The copper oxide dispersion obtained in this way can be mixed with copper particles, etc. using the method described later, and can be made into a dispersion of the present embodiment. The dispersion is used for printing and coating.

[0231] [Copper particles]

[0232] The dispersion according to the second embodiment contains copper particles having a particle size of 0.1 μm or more and 100 μm or less.

[0233] The dispersion of the third embodiment contains at least one of copper particles having a shape elongated in one direction, a dendritic shape, or a flat shape.

[0234] The reasons for using copper particles in the dispersion are as follows: since copper particles are the same metal as the metallic copper obtained by reducing cuprous oxide, copper corrosion and formation of intermetallic compounds do not occur; and the finally obtained conductive pattern has good electrical conductivity and sufficient mechanical strength.

[0235] It should be noted that the average particle size of particles having a shape extending in one direction and particles having a dendritic shape is the average particle size (median diameter, mass basis, D50) measured using a particle size distribution measuring device using a laser diffraction scattering method. In addition, the average primary particle size of particles having a flat shape is the diameter of the circle when its main surface is regarded as a circle with equal area.

[0236] The particle size of the copper particles can be determined within the scope of the present embodiment according to the shape and size of the pattern, for example, when the pattern is composed of lines, it can be determined according to the thickness and spacing thereof. In addition, the particle size of the copper particles can be determined by considering the method for forming the coating film (i.e., considering the printing method or the coating method).

[0237] In particular, in screen printing, it is important that the components contained in the dispersion, especially the copper particles, can pass through the screen without clogging, and the particle size needs to be selected in consideration of the mesh size of the plate. If the particles are too large, the screen will be clogged, and problems such as pinholes due to particle shedding and deterioration of the smoothness of the coating surface will occur. In particular, when the pattern of the coating film is composed of fine lines, a large mesh number is used in the screen, resulting in a reduction in the size of the opening, so the problem is the occurrence of pinholes caused by clogging, resulting in broken lines.

[0238] In addition to being composed of metallic copper alone, copper particles may also be formed by coating the surface of the copper particles with a copper oxide (cuprous oxide or cupric oxide) or a dissimilar metal or oxide such as silver or silver oxide, and the use of such coated particles can also fully exert the effect of suppressing the generation of cracks. That is, even if the surface of the copper particles is coated with copper oxide or silver oxide, it is easily reduced during firing, so that the conductivity of the conductive film can be ensured.

[0239] As the copper particles of the present embodiment, commercially available products may be used, or those synthesized may be used.

[0240] Regarding commercially available products, for example, copper particles having a shape extending in one direction may include electrolytic copper powder EAZ-2T manufactured by Mitsui Mining and Smelting Co., Ltd.; dendritic copper particles may include electrolytic copper powder EAX-2 manufactured by Mitsui Mining and Smelting Co., Ltd.; and flat copper particles may include 1400YP manufactured by Mitsui Mining and Smelting Co., Ltd.

[0241] [Copper particle mass ratio]

[0242] In the dispersions of the second and third embodiments, the ratio of the mass of the copper particles to the mass of the copper oxide particles (hereinafter referred to as the copper particle mass ratio) is preferably 0.5 to 10, more preferably 1.0 to 7.0, further preferably 1.5 to 6.0, and particularly preferably 2.0 to 5.0. When the copper particle mass ratio is within this range, a large amount of cuprous oxide is present, so the copper particles obtained by reduction are sufficiently bonded to each other, thereby improving the mechanical strength of the conductive film after firing. In addition, the crack suppression effect brought about by the copper particles obtained by reduction can be fully exerted.

[0243] When the dispersion contains other metal particles, the copper particle mass ratio is determined by the total of the other metal particles and the copper particles; when the dispersion contains other metal oxide particles, the copper particle mass ratio is determined by the total of the other metal oxide particles and copper oxide.

[0244] [Dispersant]

[0245] Next, the dispersant is described. As the dispersant, for example, a phosphorus-containing organic substance can be cited. The phosphorus-containing organic substance can be adsorbed on copper oxide, and in this case, aggregation is suppressed by a steric hindrance effect. In addition, the phosphorus-containing organic substance is a material that exhibits electrical insulation in an insulating region. The phosphorus-containing organic substance can be a single molecule or a mixture of two or more molecules.

[0246] In addition, the acid value of the dispersant is preferably 20 to 130. Thus, by limiting the range of the acid value of the dispersant, the dispersion stability of the dispersion can be effectively improved.

[0247] In addition, in the dispersion, the ratio of the mass of the organic compound to the mass of the copper oxide particles is preferably 0.0050 to 0.30.

[0248] The number average molecular weight of the dispersant is not particularly limited, but is preferably 300 or more, more preferably 500 or more, and further preferably 1000 or more. The number average molecular weight of the dispersant is not particularly limited, but is preferably 30,000 or less, more preferably 20,000 or less, and further preferably 10,000 or less. When the number average molecular weight of the dispersant is 300 or more, the dispersant has excellent insulation properties and tends to have increased dispersion stability of the resulting dispersion; when the number average molecular weight of the dispersant is 30,000 or less, it is easy to burn. In addition, as a structure, a phosphate ester of a high molecular weight copolymer having a group having an affinity for copper oxide is preferred. For example, the structure of chemical formula (1) adsorbs copper oxide, especially cuprous oxide, and has excellent adhesion to the substrate, so it is preferred.

[0249] [Chemistry 1]

[0250] Chemical formula (1)

[0251]

[0252] The phosphorus-containing organic material is preferably one that is easily decomposed or evaporated by light or heat. By using an organic material that is easily decomposed or evaporated by light or heat, organic residue is less likely to remain after firing, and a conductive pattern region with low resistivity can be obtained.

[0253] The decomposition temperature of the phosphorus-containing organic matter is not limited, but is preferably 600° C. or less, more preferably 400° C. or less, and further preferably 200° C. or less. The boiling point of the phosphorus-containing organic matter is not limited, but is preferably 300° C. or less, more preferably 200° C. or less, and further preferably 150° C. or less.

[0254] The absorption characteristics of the phosphorus-containing organic substance are not limited, but it is preferred that the phosphorus-containing organic substance can absorb the light used in the firing. For example, when a laser is used as a light source for firing, it is preferred to use a phosphorus-containing organic substance that can absorb the light emitted by the laser at a wavelength of, for example, 355 nm, 405 nm, 445 nm, 450 nm, 532 nm, 1056 nm. When the substrate is a resin, wavelengths of 355 nm, 405 nm, 445 nm, and 450 nm are particularly preferred.

[0255] As the dispersant, known substances can be used, for example, salts of long-chain polyaminoamide and polar acid esters, unsaturated polycarboxylic acid polyaminoamide, polycarboxylic acid salts of polyaminoamide, salts of long-chain polyaminoamide and acid polymers and other macromolecules having basic groups can be cited. In addition, alkylammonium salts, amine salts, amide amine salts and the like of macromolecules such as acrylic acid polymers, acrylic acid copolymers, modified polyester acids, polyether ester acids, polyether carboxylic acids, and polycarboxylic acids can also be cited. As such dispersants, commercially available products can also be used.

[0256] Examples of the commercially available products include DISPERBYK (registered trademark)-101, DISPERBYK-102, DISPERBYK-110, DISPERBYK-111, DISPERBYK-112, DISPERBYK-118, DISPERBYK-130, DISPERBYK-140, DISPERBYK-142, DISPERBYK-145, DISPERBYK-160, DISPERBYK-161, and DISPERBYK-162. YK-162, DISPERBYK-163, DISPERBYK-2155, DISPERBYK-2163, DISPERBYK-2164, DISPERBYK-180, DISPERBYK-2000, DIS PERBYK-2025, DISPERBYK-2163, DISPERBYK-2164, BYK-9076, BYK-9077, TERRA-204, TERRA-U (the above are manufactured by BYK Chemical Company), Flowlen DOPA-15B, Flowlen DOPA-15BHFS, Flowlen DOPA-22, Flowlen DOPA-33, Flowlen DOPA-44, Flowlen DOPA-17HF, Flowlen TG-662C, Flowlen KTG-2400 (all manufactured by Kyoeisha Chemical Co., Ltd.), ED-117, ED-118, ED-212, ED-213, ED-214, ED-216, ED-350, ED-360 (all manufactured by Kusumoto Chemicals Co., Ltd.), Plysurf M208F, Plysurf DBS (all manufactured by Dai-ichi Kogyo Seiyaku), etc. These substances may be used alone or in combination of a plurality of them.

[0257] The required amount of dispersant is proportional to the amount of copper oxide, and is adjusted in consideration of the required dispersion stability. The mass ratio (dispersant mass / copper oxide mass) of the dispersant contained in the dispersion of the present embodiment is 0.0050 or more and 0.30 or less, preferably 0.050 or more and 0.25 or less, and more preferably 0.10 or more and 0.23 or less. The amount of dispersant has an influence on the dispersion stability, and if the amount is small, it is easy to agglomerate, and if the amount is large, the dispersion stability tends to improve. However, when the content of the dispersant in the dispersion of the present embodiment is 35% by mass or less, the influence of the residue from the dispersant in the conductive film obtained by firing can be suppressed, and the conductivity can be improved.

[0258] The acid value (mgKOH / g) of the dispersant is preferably 20 to 130. More preferably, it is 30 to 100. When the acid value falls within this range, the dispersion stability is excellent, so it is preferred. It is particularly effective in the case of copper oxide with a small average particle size. Specifically, "DISPERBYK-102" (acid value 101), "DISPERBYK-140" (acid value 73), "DISPERBYK-142" (acid value 46), "DISPERBYK-145" (acid value 76), "DISPERBYK-118" (acid value 36), "DISPERBYK-180 (acid value 94), etc. manufactured by BYK Chemical Company can be cited.

[0259] In addition, the difference between the amine value (mgKOH / g) and the acid value of the dispersant (amine value-acid value) is preferably -50 or more and 0 or less. The amine value represents the total amount of free alkali and alkali, and the acid value represents the total amount of free fatty acid and fatty acid. The amine value and the acid value are measured by a method according to JIS K7700 or ASTM D2074. When the difference is -50 or more and 0 or less, the dispersion stability is excellent, so it is preferred. The difference is more preferably -40 or more and 0 or less, and further preferably -20 or more and 0 or less.

[0260] [reducing agent]

[0261] Next, the reducing agent is described. As the reducing agent, hydrazine, hydrazine hydrate, sodium, carbon, potassium iodide, oxalic acid, iron sulfide (II), sodium thiosulfate, ascorbic acid, tin chloride (II), diisobutylaluminum hydride, formic acid, sodium borohydride, sulfite, etc. can be cited. From the aspect of contributing to the reduction of copper oxide, especially cuprous oxide, during firing, and being able to produce a copper film with lower resistance, the reducing agent is most preferably hydrazine or hydrazine hydrate. In addition, by using hydrazine or hydrazine hydrate, the dispersion stability of the dispersion can be maintained, and the resistance of the copper film can be reduced.

[0262] The required amount of the reducing agent is proportional to the amount of copper oxide and is adjusted in consideration of the required reducibility. The mass ratio of the reducing agent contained in the dispersion of the present embodiment (reducing agent mass / copper oxide mass) is preferably 0.0001 to 0.10, more preferably 0.0001 to 0.05, and further preferably 0.0001 to 0.03. When the mass ratio of the reducing agent is 0.0001 or more, the dispersion stability is improved and the resistance of the copper film is reduced. In addition, when the mass ratio is 0.10 or less, the long-term stability of the dispersion is improved.

[0263] [Dispersion medium]

[0264] The dispersion of the present embodiment may contain a dispersion medium (solvent) in addition to the above-mentioned components.

[0265] The dispersion medium used in the dispersions of the first to third embodiments is preferably at least one selected from the group consisting of terpineol, γ-butyrolactone, cyclohexanone, ethanol, propylene glycol, butanol, propanol, ethylene glycol monoethyl ether acetate, and tetralin. In addition, it is more preferred that two or more of these dispersion media are contained.

[0266] These dispersion media have high boiling points and thus exhibit an effect of improving printing continuity. These dispersion media may have a reducing action, but when the above-mentioned reducing agent is contained in the dispersion, it functions as a dispersion medium.

[0267] Regarding the dispersion medium used in the first to third embodiments, from the perspective of dispersion, it is preferably selected from a dispersion medium in which the dispersant can be dissolved. On the other hand, from the perspective of using the dispersion to form a conductive pattern, in order to prevent the volatility of the dispersion medium from affecting the workability, it is necessary to make it suitable for the formation method of the conductive pattern, such as a method suitable for printing or coating. Therefore, the dispersion medium can be selected from the following solvents based on the dispersibility and the workability of printing or coating.

[0268] Specific examples of the dispersion medium include the following solvents: propylene glycol monomethyl ether acetate, 3-methoxy-3-methyl-butyl acetate, ethoxyethyl propionate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol tert-butyl ether, dipropylene glycol monomethyl ether, ethylene glycol butyl ether, ethylene glycol ethyl ether, ethylene glycol methyl ether, ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2-pentanediol, 2-methylpentane-2,4-diol, 2,5-hexanediol, 2,4-heptanediol, 2-ethylhexane-1,3-diol, diethylene glycol, hexanediol, octanediol, triethylene glycol, tri-1,2-propylene glycol, glycerol, ethylene glycol monohexyl ether, diethylene glycol monoethyl ether , diethylene glycol monobutyl ether, ethylene glycol monobutyl acetate, diethylene glycol monoethyl ether acetate, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, 2-butanol, tert-butanol, n-pentanol, isopentanol, 2-methylbutanol, 2-pentanol, tert-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, 1-hexanol, 2-hexanol, 2-ethylbutanol, 1-heptanol, 2-heptanol, 3-heptanol, n-octanol, 2-ethylhexanol, 2-octanol, n-nonanol, 2,6-dimethyl-4-heptanol, n-decanol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, diacetone alcohol, etc. In addition to the solvents specifically described above, alcohols, glycols, glycol ethers, and glycol ester solvents can also be used in the dispersion medium. These may be used alone or in combination, and may be selected according to the printing method in consideration of evaporation, printing machine materials, and solvent resistance of the printed substrate.

[0269] As the dispersion medium, a monoalcohol having a carbon number of 10 or less is more preferred, and a monoalcohol having a carbon number of 8 or less is further preferred. Among the monoalcohols having a carbon number of 8 or less, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, and tert-butanol are particularly suitable for their dispersibility, volatility, and viscosity, and are therefore more preferred. These monoalcohols can be used alone or in combination. In order to suppress the reduction in the dispersibility of copper oxide and to further disperse it more stably through interaction with the dispersant, the monoalcohol preferably has a carbon number of 8 or less. In addition, when the carbon number is selected to be 8 or less, the resistance value is also reduced, which is preferred.

[0270] Among them, the boiling point affects the workability of the solvent. If the boiling point is too low, the volatilization is fast, so the increase in defects caused by the precipitation of solid substances or the increase in the cleaning frequency deteriorates the workability. Therefore, in the coating and dispenser method, the boiling point is above 40°C; in the inkjet method, the screen method, and the flat plate method, the boiling point can be above 120°C, more preferably above 150°C, and further preferably above 200°C; as the upper limit of the boiling point, it is preferably below 300°C from the perspective of drying.

[0271] [Preparation of dispersion containing copper oxide and copper]

[0272] The dispersion containing cuprous oxide and copper particles, i.e., the dispersion can be prepared as follows: copper fine particles and, if necessary, a dispersion medium are mixed in the above-mentioned cupric oxide dispersion at a prescribed ratio, and a dispersion treatment is performed using, for example, a mixer method, an ultrasonic method, a three-roll method, a double-roll method, an attritor, a homogenizer, a Banbury mixer, a paint stirrer, a kneader, a ball mill, a sand mill, a rotation-revolution mixer, etc., thereby preparing the dispersion.

[0273] Since part of the dispersion medium is contained in the already prepared copper oxide dispersion, it is not necessary to add it in this step if the amount contained in the copper oxide dispersion is sufficient. If a reduction in viscosity is required, it can be added in this step as needed. Alternatively, it can be added after this step. The dispersion medium can be the same as the dispersion medium added when preparing the copper oxide dispersion, or a different dispersion medium can be added.

[0274] In addition, an organic binder, an antioxidant, a reducing agent, metal particles, metal oxides may be added as necessary, and metals or metal oxides, metal salts and metal complexes may be contained as impurities.

[0275] In addition, regarding metal filament-shaped, dendritic, and scaly copper particles, in order to increase the crack prevention effect, multiple types of spherical, dice-shaped, polyhedral, etc. copper particles or other metals can be added alone or in combination, and their surfaces can be covered with oxides or other metals with good conductivity such as silver.

[0276] In addition, when the shape of the metal particles other than copper added is one or more of the metal wire, dendrite, and scale, since they have the same crack prevention effect as copper particles of the same shape, they can also replace part of the copper particles of the same shape or be added to the copper particles of the same shape for use, but it is necessary to consider migration, particle strength, resistance value, copper corrosion, formation of intermetallic compounds, cost, etc. Examples of metal particles other than copper include gold, silver, tin, zinc, nickel, platinum, bismuth, indium, and antimony.

[0277] As metal oxide particles, cuprous oxide can be replaced with silver oxide, cupric oxide, etc., or they can be used in addition. However, similarly to the case of metal particles, migration, particle strength, resistance value, copper corrosion, formation of metal compounds, cost, etc. need to be considered. The addition of these metal particles and metal oxide particles can be used for the adjustment of the sintering, resistance, conductor strength, absorbance during light firing of the conductive film, etc. Even if these metal particles and metal oxide particles are added, cracks can still be fully suppressed due to the presence of metal filaments, dendrites, and flaky copper particles. These metal particles and metal oxide particles can be used alone or in combination of two or more, and there is no restriction on the shape. For example, silver or silver oxide can expect effects such as reduced resistance or reduced firing temperature.

[0278] However, silver is a precious metal. From the perspective of cost increase and crack prevention, the amount of silver added is preferably not more than the range of wire-shaped, dendritic, and flaky copper particles. In addition, tin has a low cost and a low melting point, so it has the advantage of easy sintering. However, it has a tendency to increase resistance. From the perspective of crack prevention, it is also preferred that the amount of tin added is not more than the range of wire-shaped, dendritic, and flaky copper particles and cuprous oxide. Copper oxide acts as a light absorber and a heat ray absorber in methods using light or infrared rays such as flash lamps or lasers. However, from the perspective of preventing peeling from the substrate due to the large amount of gas generated during reduction, copper oxide is preferably added less than cuprous oxide.

[0279] In this embodiment, even if metals other than copper, copper particles other than metal wires, dendrites, or scales, and metal oxides other than copper oxide are included, the crack prevention effect and the effect of improving the stability of resistance over time can be exerted. However, the amount of metals other than copper, copper particles other than metal wires, dendrites, or scales, and metal oxides other than copper oxide added is preferably less than the amount of copper particles in the form of metal wires, dendrites, or scales and copper oxide. In addition, the addition ratio of metals other than copper, copper particles other than metal wires, dendrites, or scales, and metal oxides other than copper oxide to copper particles in the form of metal wires, dendrites, or scales and copper oxide can be 50% or less, more preferably 30% or less, and even more preferably 10% or less.

[0280] [Details of the structure with conductive pattern]

[0281] Hereinafter, each configuration of the structure 10 with a conductive pattern according to the present embodiment will be described in detail. However, each configuration is not limited to the specific examples given below.

[0282] The method for producing a structure with a conductive pattern according to the present embodiment includes a step of applying the dispersion according to the present embodiment on a substrate to form a coating film, and a step of irradiating the coating film with laser light to form a conductive pattern on the substrate.

[0283] In addition, the method for manufacturing a structure with a conductive pattern of the present embodiment comprises a step of applying a dispersion on a substrate in a desired pattern to form a coating film, and a step of firing the coating film to form a conductive pattern on the substrate. According to the method of the present embodiment, the coating liquid can be directly formed on the substrate in a desired pattern, so that the productivity can be improved compared with the existing method using a photoresist.

[0284] [Method for coating dispersion on substrate]

[0285] The coating method using copper oxide ink as a dispersion is described. There are no particular limitations on the coating method, and a printing method such as an aerosol method, screen printing, gravure direct printing, gravure offset printing, flexographic printing, offset printing, or a dispenser drawing method can be used. As a coating method, a die coating, spin coating, slit coating, rod coating, blade coating, spray coating, dip coating, or the like can be used.

[0286] [Substrate]

[0287] The substrate used in the present embodiment has a surface for forming a coating film, which may have a plate shape or may be a three-dimensional object. The substrate in the present embodiment refers to a substrate material for forming a circuit substrate sheet of a wiring pattern or a housing material of a housing with wiring, etc. As an example of a housing, housings of electrical devices such as mobile phone terminals, smart phones, dimming glass, televisions, personal computers, etc. may be cited. In addition, as other examples of housings, dashboards, instrument panels, steering wheels, chassis, etc. may be cited in the automotive field.

[0288] The substrate used in this embodiment is not particularly limited, and is made of an inorganic material or an organic material.

[0289] Examples of the inorganic material include glasses such as soda-lime glass, alkali-free glass, borosilicate glass, and quartz glass, and ceramic materials such as alumina.

[0290] As the organic material, polymer materials, paper, etc. can be mentioned. As the polymer material, a resin film can be used, and polyimide (PI), polyethylene terephthalate (PET), polyether sulfone (PES), polyethylene naphthalate (PEN), polyester, polycarbonate (PC), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyacetal (POM), polyarylate (PAR), polyamide (PA), polyamideimide (PAI), polyetherimide (PEI), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyphenylene sulfide (PPS), polyether ketone (PEK), polyphthalamide (PPA), polyether nitrile (PEN), polybenzimidazole (PBI), polycarbodiimide, polysiloxane, polymethacrylamide, nitrile rubber, acrylonitrile rubber, polytetrafluoroethylene, epoxy resin, phenol resin, melamine resin, urea resin, polymethyl methacrylate resin (PMMA), Polybutene, polypentene, ethylene-propylene copolymer, ethylene-butylene-diene copolymer, polybutadiene, polyisoprene, ethylene-propylene-diene copolymer, butyl rubber, polymethylpentene (PMP), polystyrene (PS), styrene-butadiene copolymer, polyethylene (PE), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polyetheretherketone (PEEK), novolac, benzocyclobutene, polyvinylphenol, polychloropyrene, polyoxymethylene, polysulfone (PSF), polyphenylsulfone resin (PPSU), cycloolefin polymer (COP), acrylonitrile-butadiene-styrene resin (ABS), acrylonitrile-styrene resin (AS), nylon resin (PA6, PA66), polybutylene terephthalate resin (PBT), polyethersulfone resin (PESU), polytetrafluoroethylene resin (PTFE), polychlorotrifluoroethylene (PCTFE), silicone resin, etc. In particular, PI, PET and PEN are preferred from the aspects of flexibility and cost.

[0291] As paper, there can be cited foreign papers such as fiberless paper, medium-quality paper, coated paper, cardboard, and corrugated paper made of common pulp as raw materials; and paper made of cellulose nanofibers as raw materials. In the case of paper, paper in which a polymer material is dissolved, or paper in which a sol-gel material is impregnated and solidified can be used. In addition, these materials can also be used by laminating and bonding. For example, there can be cited paper phenol substrates, paper epoxy substrates, glass composite substrates, glass epoxy substrates and other composite substrates, Teflon (registered trademark) substrates, alumina substrates, low temperature and low humidity co-fired ceramics (LTCC), silicon wafers, etc.

[0292] The thickness of the substrate can be, for example, 1 μm to 10 mm, preferably 25 μm to 250 μm. When the thickness of the substrate is 250 μm or less, the electronic device produced can be lightweight, space-saving and flexible, and thus it is preferred. When the substrate is a housing, its thickness can be, for example, 1 μm to 10 mm, preferably 200 μm to 5 mm. The inventors have clearly stated that by selecting this range, mechanical strength and heat resistance after molding can be exhibited.

[0293] [Formation of Conductive Pattern]

[0294] As a method for forming a conductive pattern, there are the following methods: 1) a method of using the above-mentioned printing method and firing after making a pattern; and 2) a method of applying a dispersion to the entire surface of a substrate and laser drawing thereon in a manner to form a specific pattern to make a pattern. In both 1) and 2), a portion of the copper oxide is not reduced and remains on the substrate side, which can improve the adhesion between the conductive pattern and the substrate, and is therefore preferred. In addition, the conductive pattern is a wiring, and the wiring width is preferably 0.5 μm to 10000 μm, more preferably 1 μm to 1000 μm, and further preferably 1 μm to 500 μm. In addition, the conductive pattern can be formed in a mesh shape. The mesh and lattice wiring improves the transmittance and is transparent, and is therefore preferred.

[0295] [Firing of dispersion]

[0296] There is no particular limitation on the method of firing treatment as long as a conductive film that exerts the effect of the present invention can be formed. As specific examples, methods using an incinerator, a plasma firing method, a photo-firing method, etc. can be cited. In the laser irradiation in the photo-firing, a coating film is formed using copper oxide ink as a dispersion, and the coating film is irradiated with a laser, thereby firing and patterning the copper particles at one time. In other firing methods, a desired pattern can be printed using a dispersion, which is fired to obtain a conductive pattern. When making a conductive pattern, a portion of the cuprous oxide is not reduced and remains on the contact surface with the substrate, thereby improving the adhesion of the conductive pattern to the substrate, and is therefore preferred.

[0297] [Firing furnace]

[0298] In the present embodiment, in the firing method using a firing furnace, copper oxide is reduced to form copper and the copper is sintered, so the coating film is fired with heat of 100° C. or higher, preferably 150° C. or higher, and more preferably 200° C. or higher.

[0299] In the method of firing using a firing furnace that is easily affected by oxygen, it is preferred to process the coating of the dispersion in a non-oxidizing atmosphere. In addition, when copper oxide is not easily reduced using only the organic components contained in the dispersion, it is preferred to fire under a reducing atmosphere. A non-oxidizing atmosphere refers to an atmosphere that does not contain oxidizing gases such as oxygen, for example, an atmosphere filled with inert gases such as nitrogen, argon, helium, and neon. In addition, a reducing atmosphere refers to an atmosphere in which reducing gases such as hydrogen and carbon monoxide exist, but it can also be mixed with an inert gas. These gases can be filled into a firing furnace, and the coating of the dispersion can be fired in a closed system or while the gas is continuously circulated. In addition, firing can be carried out in a pressurized atmosphere or in a reduced pressure atmosphere.

[0300] [Plasma firing method]

[0301] Compared with the method using a firing furnace, the plasma method of this embodiment can be processed at a lower temperature, and is one of the more preferred methods as a firing method when a resin film with low heat resistance is used as a substrate. In addition, since the organic substances on the pattern surface or the oxide film can be removed by plasma, it also has the advantage of ensuring good weldability. Specifically, it is the following method: a reducing gas or a mixed gas of a reducing gas and an inert gas is circulated in a chamber, a plasma is generated by microwaves, and the active species thus generated are used as a heating source required for reduction or sintering, and further used for decomposing organic substances contained in a dispersant, etc., to obtain a conductive film.

[0302] Especially in the metal part, the active species are mostly deactivated, the metal part can be selectively heated, and the temperature of the substrate itself is not easy to increase, so it is also suitable for resin film as a substrate. The dispersion contains copper as a metal, and copper oxide changes into copper as the firing proceeds, so only the heating of the pattern part is promoted. In addition, if organic matter as a dispersant or binder component remains in the conductive pattern, it will hinder sintering and the resistance tends to increase, but in the plasma method, the removal effect of organic matter in the conductor pattern is large. The plasma method can remove organic matter and oxide film on the surface of the coating, so it has the advantage of being able to effectively improve the weldability of the conductive pattern.

[0303] As the reducing gas component, hydrogen or the like can be used, and as the inert gas component, nitrogen, helium, argon or the like can be used. These components can be used alone, or the reducing gas component and the inert gas component can be mixed in any proportion for use. In addition, two or more inert gas components can also be mixed for use.

[0304] Plasma firing method can adjust microwave input power, introduced gas flow rate, chamber pressure, distance from plasma source to processed sample, processed sample temperature, and processing time, and the intensity of processing can be changed by these adjustments. Therefore, if the above adjustment items are optimized, it is needless to say that a conductive film with low resistance can be obtained by using a substrate of inorganic material, and a conductive film with low resistance can also be obtained by using a thermosetting resin film, paper, and a thermoplastic resin film with low heat resistance, such as PET and PEN, of organic material as a substrate. However, since the optimal conditions vary according to the device structure and the type of sample, they are adjusted according to the situation.

[0305] [Photo-firing method]

[0306] The light burning method of this embodiment can be applied to a flash method or a laser method using a discharge tube such as a xenon as a light source. These methods are the following methods: a method of exposing a dispersion coated on a substrate to a high temperature in a short time by exposing it to high-intensity light for a short time to form a conductive film by reducing copper oxide, sintering copper particles, integrating them, and decomposing organic components. Since the burning time is extremely short, it can be applied to a resin film substrate with low heat resistance in a method with little damage to the substrate.

[0307] The flash method is a method in which a large amount of pulsed light is generated by using a xenon discharge tube to instantly discharge the charge accumulated in the capacitor, and the dispersion formed on the substrate is irradiated, thereby instantly heating the copper oxide to a high temperature and changing it into a conductive film. The exposure amount can be adjusted by the light intensity, light emission time, light irradiation interval, and number of times. As long as the substrate has high light transmittance, a conductive pattern based on the dispersion can be formed even on a resin substrate with low heat resistance, such as PET, PEN, or paper.

[0308] Although the light sources are different, the same effect can be obtained even if a laser source is used. In the case of a laser, in addition to the adjustment items of the flash mode, there is also the freedom of wavelength selection, and the light absorption wavelength of the dispersion that forms the pattern or the absorption wavelength of the substrate can also be considered for selection. In addition, it has the following characteristics: exposure can be performed by beam scanning, and the exposure range can be easily adjusted, such as exposure on the entire surface of the substrate, or selection of partial exposure. As types of lasers, YAG (yttrium aluminum garnet), YVO (yttrium vanadate), Yb (ytterbium), semiconductor lasers (GaAs, GaAlAs, GaInAs), carbon dioxide, etc. can be used, and not only the fundamental wave can be taken out, but also the harmonics can be taken out for use when necessary.

[0309] In particular, when using laser, the wavelength of the emitted light is preferably 300 nm or more and 1500 nm or less. For example, 355 nm, 405 nm, 445 nm, 450 nm, 532 nm, 1056 nm, etc. When the substrate or the housing is a resin, laser wavelengths of 355 nm, 405 nm, 445 nm, 450 nm, and 532 nm are particularly preferred from the absorption region of the layer containing copper oxide in this embodiment. By using laser, the desired pattern can be freely made into a plane or a three-dimensional shape.

[0310] The surface roughness of the conductive layer or the conductive pattern is preferably 500 nm to 4000 nm, more preferably 750 nm to 3000 nm, and even more preferably 1000 nm to 2000 nm. When the surface roughness falls within this range, the solder layer is easily attached to the conductive pattern, and the adhesion between the conductive pattern and the solder layer is improved.

[0311] [Formation of solder layer on conductive pattern]

[0312] In the structure with a conductive pattern made using the dispersion of the present embodiment, since the dispersant and dispersion medium that deteriorate the solderability are decomposed during the firing process, when the body to be joined (such as an electronic component, etc.) is soldered to the conductive pattern, it has the advantage that the molten solder is easily attached. Here, solder refers to an alloy with lead and tin as the main components, and also includes lead-free solder that does not contain lead. Since the conductive pattern of the present embodiment has a vacant wall (void), the solder enters the void, thereby improving the adhesion between the conductive pattern and the solder layer.

[0313] The grain size of copper contained in the conductive pattern and the conductive layer is preferably 0.1 μm to 100 μm, more preferably 0.5 μm to 50 μm, and particularly preferably 1.0 μm to 10 μm. This improves adhesion between the conductive pattern and the solder layer.

[0314] In this embodiment, the electronic components are active components such as semiconductors, integrated circuits, diodes, liquid crystal displays, etc.; passive components such as resistors and capacitors; and at least one of mechanical components such as connectors, switches, wires, radiators, antennas, etc.

[0315] In addition, the formation of the solder layer on the conductive pattern is preferably performed by a reflow method. In the reflow method, first, during soldering, Figure 3 (j) and Figure 4 (l) A solder paste (paste solder) is applied to a portion of the conductive pattern area formed in (l), for example, on the surface of the pad. The solder paste is applied by contact printing using a metal mask and a metal scraper, for example. Thus, a solder layer is formed on a portion of the surface of the conductive pattern. That is, Figure 3 After the step (j), a structure with a conductive pattern is obtained in which a solder layer is formed on a part of the surface of the conductive pattern in the surface layer. Figure 4 After step (1), a structure with a conductive pattern is obtained in which a solder layer is formed on a part of the surface of the conductive pattern. The area of ​​the part of the surface of the conductive pattern where the solder layer is formed is not particularly limited as long as it is an area that can bond the conductive pattern to the electronic component.

[0316] (Joining of electronic components)

[0317] Next, the electronic component is placed on the conductive substrate in a state where the portion to be joined of the electronic component is in contact with a portion of the applied solder paste (solder layer). After that, the conductive substrate with the electronic component placed thereon is heated in a reflow furnace to solder a portion of the conductive pattern area (solder pad, etc.) to the portion to be joined of the electronic component. Fig. 9 It is a top view of the structure with a conductive pattern on which a solder layer is formed according to the present embodiment. Fig. 9 A shows a photograph of a structure with a conductive pattern on which a solder layer is formed. Fig. 9 B shows its schematic diagram.

[0318] like Fig. 9 As shown, a conductive pattern B is formed on a flexible substrate 11, and the conductive pattern B is formed by firing a copper oxide ink as a dispersion. A solder layer 20 is formed on the surface of the conductive pattern B. The conductive pattern B and the wire 90 are appropriately soldered by the solder layer 20, and the conductive pattern B and the electronic component 91 are appropriately connected by the wire 90.

[0319] According to the method for manufacturing a structure with a conductive pattern of the present embodiment, since the copper oxide ink as a dispersion is fired to form a conductive pattern, the organic binder contained in the dispersion is decomposed, thereby improving the wettability of the solder in the obtained conductive pattern, and a solder layer can be easily formed on the surface of the conductive pattern. Therefore, the soldering of electronic components can be performed. As a result, it is possible to prevent the solder layer that joins the conductive pattern area with the joined portion of the electronic component from being defective, and a structure with a conductive pattern to which the electronic component is soldered can be manufactured with a high yield.

[0320] In addition, according to the method for manufacturing a structure with a conductive pattern of the second embodiment, in a coating film formed using a dispersion containing copper oxide particles with a particle size of 1 nm to 50 nm, copper particles with a particle size of 0.1 μm to 100 μm, and an organic compound having a phosphate group, since the wettability of the solder is high, after the molten solder is coated on the metal surface, the solder can be prevented from being disconnected or from forming a very thin portion of the solder, i.e., dewetting. As a result, the occurrence of defects in the solder joint portion where the conductive film is joined to the joined portion of the electronic component can be prevented, and the substrate with the electronic component can be manufactured with a high yield.

[0321] Example

[0322] The present invention will be specifically described below by way of examples and comparative examples, but the present invention is not limited to these examples and comparative examples.

[0323] <Experimental Example 1>

[0324] [Hydrazine quantitative method]

[0325] Quantification of hydrazine was performed by the standard addition method.

[0326] Add 33 μg of hydrazine and the surrogate substance (hydrazine) to 50 μL of the sample (copper nano-ink). 15 N2H4) 33μg, benzaldehyde 1% acetonitrile solution 1ml. Finally, add 20μL of phosphoric acid, and perform GC / MS measurement after 4 hours.

[0327] Similarly, 66 μg of hydrazine and the surrogate substance (hydrazine) were added to 50 μL of the sample (copper nano ink). 15 N2H4) 33μg, benzaldehyde 1% acetonitrile solution 1ml. Finally, add 20μL of phosphoric acid, and perform GC / MS measurement after 4 hours.

[0328] Similarly, 133 μg of hydrazine and the surrogate substance (hydrazine) were added to 50 μL of the sample (copper nano ink). 15N2H4) 33μg, benzaldehyde 1% acetonitrile solution 1ml. Finally, add 20μL of phosphoric acid, and perform GC / MS measurement after 4 hours.

[0329] Finally, hydrazine was not added to 50 μL of the sample (copper nano-ink) but an alternative substance (hydrazine) was added. 15 N2H4) 33μg, benzaldehyde 1% acetonitrile solution 1ml, and finally phosphoric acid 20μL were added, and GC / MS measurement was performed after 4 hours.

[0330] The peak area value of hydrazine was determined from the chromatogram of m / z = 207 according to the GC / MS measurement of the above four points. The peak area value of the substitute was then determined from the mass spectrum of m / z = 209. The x-axis was the weight of the added hydrazine / the weight of the added substitute, and the y-axis was the peak area value of hydrazine / the peak area value of the substitute, to obtain a calibration curve based on the standard addition method.

[0331] The value of the Y slice obtained from the calibration curve is divided by the weight of hydrazine added / the weight of the replacement substance added to obtain the weight of hydrazine.

[0332] [Particle size measurement]

[0333] The average secondary particle size of the copper oxide ink as a dispersion was measured by the cumulative method using FPAR-1000 manufactured by Otsuka Electronics.

[0334] (Example 1)

[0335] 806 g of copper (II) acetate monohydrate (manufactured by Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 7560 g of distilled water (manufactured by Kyoei Pharmaceutical Co., Ltd.) and 3494 g of 1,2-propylene glycol (manufactured by Kanto Chemical Co., Ltd.), and the liquid temperature was set to -5°C using an external thermostat. 235 g of hydrazine monohydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the obtained solution over 20 minutes, and after stirring for 30 minutes, the liquid temperature was set to 25°C using an external thermostat and stirred for 90 minutes. After stirring, the obtained dispersion was separated into a supernatant and a precipitate by centrifugal separation. To 390 g of the obtained precipitate were added 54.8 g of DisperBYK-145 (manufactured by BYK Chemicals), 13.7 g of Surflon S611 (manufactured by Seimi Chemicals), and 907 g of ethanol (manufactured by Kanto Chemical Co., Ltd.), and dispersed using a homogenizer to obtain 1365 g of a cuprous oxide dispersion (copper oxide ink).

[0336] The dispersion liquid was well dispersed, the content of cuprous oxide was 20%, the average secondary particle size was 22 nm, and the hydrazine content was 3000 ppm.

[0337] (Example 2)

[0338] 806 g of copper (II) acetate monohydrate (manufactured by Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 7560 g of distilled water (manufactured by Kyoei Pharmaceutical Co., Ltd.) and 3494 g of 1,2-propylene glycol (manufactured by Kanto Chemical Co., Ltd.), and the liquid temperature was set to -5°C using an external thermostat. 235 g of hydrazine monohydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the obtained solution over 20 minutes, and after stirring for 30 minutes, the liquid temperature was set to 25°C using an external thermostat and stirred for 90 minutes. After stirring, the obtained dispersion was separated into a supernatant and a precipitate by centrifugal separation. 54.8 g of DisperBYK-145 (manufactured by BYK Chemical), 13.7 g of Surflon S611 (manufactured by Seimi Chemical) and 907 g of ethanol (manufactured by Kanto Chemical Co., Ltd.) were added to the obtained precipitate 390 g, and dispersed using a homogenizer to obtain 1365 g of cuprous oxide dispersion. It was further bubbled with air.

[0339] The dispersion liquid was well dispersed, the content of cuprous oxide was 20%, the average secondary particle size was 25 nm, and the hydrazine content was 700 ppm.

[0340] (Example 3)

[0341] To 98.5 g of the dispersion obtained in Example 1, 1.5 g of hydrazine (manufactured by Tokyo Chemical Industry Co., Ltd.) was added.

[0342] The dispersion liquid was well dispersed, the content of cuprous oxide was 20%, the average secondary particle size was 29 nm, and the hydrazine ratio was 18000 ppm.

[0343] (Example 4)

[0344] 806 g of copper (II) acetate monohydrate (manufactured by Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 7560 g of distilled water (manufactured by Kyoei Pharmaceutical Co., Ltd.) and 3494 g of 1,2-propylene glycol (manufactured by Kanto Chemical Co., Ltd.), and the liquid temperature was set to -5°C using an external thermostat. 235 g of hydrazine monohydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the resulting solution over 20 minutes, and after stirring for 30 minutes, the liquid temperature was set to 25°C using an external thermostat, and stirred for 90 minutes. After stirring, the resulting dispersion was separated into a supernatant and a precipitate by centrifugal separation. 1.37 g of DisperBYK-145 (manufactured by BYK Chemicals), 13.7 g of Surflon S611 (manufactured by Seimi Chemicals) and 960 g of ethanol (manufactured by Kanto Chemical Co., Ltd.) were added to 390 g of the obtained precipitate, and dispersed using a homogenizer to obtain 1365 g of a cuprous oxide dispersion (copper oxide ink).

[0345] The dispersion liquid was well dispersed, the content of cuprous oxide was 20%, the average secondary particle size was 32 nm, and the hydrazine content was 3000 ppm.

[0346] (Example 5)

[0347] 806 g of copper (II) acetate monohydrate (manufactured by Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 7560 g of distilled water (manufactured by Kyoei Pharmaceutical Co., Ltd.) and 3494 g of 1,2-propylene glycol (manufactured by Kanto Chemical Co., Ltd.), and the liquid temperature was set to -5°C using an external thermostat. 235 g of hydrazine monohydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the obtained solution over 20 minutes. After stirring for 30 minutes, the liquid temperature was set to 25°C using an external thermostat and stirred for 90 minutes. After stirring, the obtained dispersion was separated into a supernatant and a precipitate by centrifugation. To 390 g of the obtained precipitate were added 82.2 g of DisperBYK-145 (manufactured by BYK Chemicals), 13.7 g of Surflon S611 (manufactured by Seimi Chemicals), and 880 g of ethanol (manufactured by Kanto Chemical Co., Ltd.), and dispersed using a homogenizer to obtain 1365 g of a cuprous oxide dispersion (copper oxide ink).

[0348] The dispersion liquid was well dispersed, the content of cuprous oxide was 20%, the average secondary particle size was 32 nm, and the hydrazine content was 3000 ppm.

[0349] (Comparative Example 1)

[0350] 4 g of cuprous oxide (MP-CU2O-25 manufactured by EM Japan), 0.8 g of DisperBYK-145 (manufactured by BYK Chemical), and 0.2 g of Surflon S611 (manufactured by Seimi Chemical) were added to 15 g of ethanol (manufactured by Kanto Chemical Co., Ltd.), and dispersed with a homogenizer to obtain 20 g of a cuprous oxide dispersion.

[0351] Agglomeration of copper oxide particles was observed in a part of the dispersion. The content of cuprous oxide was 20%, the average secondary particle size was 190 nm, and the hydrazine ratio was 0 ppm.

[0352] (Comparative Example 2)

[0353] To 97 g of the dispersion obtained in Example 1, 3 g of hydrazine (manufactured by Tokyo Chemical Industry Co., Ltd.) was added.

[0354] The copper oxide particles in the dispersion were agglomerated and could not be made into ink. The content of cuprous oxide was 20%. The hydrazine content was 33000 ppm.

[0355] (Comparative Example 3)

[0356] 806 g of copper (II) acetate monohydrate (manufactured by Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 7560 g of distilled water (manufactured by Kyoei Pharmaceutical Co., Ltd.) and 3494 g of 1,2-propylene glycol (manufactured by Kanto Chemical Co., Ltd.), and the liquid temperature was set to -5°C using an external thermostat. 235 g of hydrazine monohydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the obtained solution over 20 minutes, and after stirring for 30 minutes, the liquid temperature was set to 25°C using an external thermostat and stirred for 90 minutes. After stirring, the obtained dispersion was separated into a supernatant and a precipitate by centrifugal separation. To 390 g of the obtained precipitate were added 0.82 g of DisperBYK-145 (manufactured by BYK Chemicals), 13.7 g of Surflon S611 (manufactured by Seimi Chemicals), and 960 g of ethanol (manufactured by Kanto Chemical Co., Ltd.), and dispersed using a homogenizer to obtain 1365 g of a cuprous oxide dispersion (copper oxide ink).

[0357] The copper oxide particles in the dispersion were agglomerated and could not be made into ink. The content of cuprous oxide was 20%. The content of hydrazine was 3000 ppm.

[0358] (Comparative Example 4)

[0359] 806 g of copper (II) acetate monohydrate (manufactured by Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 7560 g of distilled water (manufactured by Kyoei Pharmaceutical Co., Ltd.) and 3494 g of 1,2-propylene glycol (manufactured by Kanto Chemical Co., Ltd.), and the liquid temperature was set to -5°C using an external thermostat. 235 g of hydrazine monohydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the obtained solution over 20 minutes, and after stirring for 30 minutes, the liquid temperature was set to 25°C using an external thermostat and stirred for 90 minutes. After stirring, the obtained dispersion was separated into a supernatant and a precipitate by centrifugal separation. To 390 g of the obtained precipitate were added 110 g of DisperBYK-145 (manufactured by BYK Chemicals), 13.7 g of Surflon S611 (manufactured by Seimi Chemicals), and 851 g of ethanol (manufactured by Kanto Chemical Co., Ltd.), and dispersed using a homogenizer to obtain 1365 g of a cuprous oxide dispersion (copper oxide ink).

[0360] The copper oxide particles in the dispersion were agglomerated and could not be made into ink. The content of cuprous oxide was 20%. The content of hydrazine was 3000 ppm.

[0361] [Reverse printing]

[0362] Using copper oxide ink, a patterned coating is formed on a substrate by reverse printing. First, a coating of copper oxide ink with uniform thickness is formed on the surface of a rubber blanket (transfer body). The surface material of the rubber blanket is usually made of silicone rubber, and it is confirmed whether the copper oxide ink adheres well to the silicone rubber and forms a uniform coating. Next, the surface of the rubber blanket with the coating of copper oxide ink formed on the surface is pressed against a relief plate to make it contact, so that a part of the coating of copper oxide ink on the surface of the rubber blanket adheres and transfers to the surface of the convex part of the relief plate. Thus, a printed pattern is formed on the coating of copper oxide ink remaining on the surface of the rubber blanket. Next, the rubber blanket in this state is pressed against the surface of the printed substrate, and the coating of copper oxide ink remaining on the rubber blanket is transferred to form a patterned coating. The evaluation criteria are as follows.

[0363] A: Reverse printing is possible.

[0364] B: The printed pattern is not formed partially.

[0365] C: Reverse printing is not possible.

[0366] [Resistance measurement]

[0367] A 600 nm thick film was made on the PEN film using a bar coater, and the copper film was reduced by heating and firing at 1.5 kW for 420 seconds using a plasma firing device. The volume resistivity of the conductive film was measured using a low resistivity meter Loresta GP manufactured by Mitsubishi Chemical. The performance results of the copper oxide ink and the coating are listed in Table 1.

[0368]

[0369] In Examples 1 to 5, the copper oxide ink did not aggregate, and a low resistance was maintained when a copper film was produced on a PEN film. In the examples, the value of (reducing agent mass / copper oxide mass) was 0.0001 or more and 0.10 or less, and the value of (dispersant mass / copper oxide mass) was 0.0050 or more and 0.30 or less. It is believed that by using hydrazine as a reducing agent, the reduction of copper oxide was promoted, and a copper film with low resistance was produced.

[0370] In contrast, in Comparative Example 1, where the value of (reducing agent mass / copper oxide mass) was less than 0.001, agglomeration of copper oxide particles was observed in a portion of the dispersion. In addition, a copper film could not be obtained by plasma firing, and resistance could not be measured. In addition, in Comparative Example 2, where the value of (reducing agent mass / copper oxide mass) was greater than 0.1, the copper oxide ink agglomerated, and thus reverse printing and resistance measurement could not be performed. In addition, in Comparative Example 3, where the value of (dispersant mass / copper oxide mass) was less than 0.005, and in Comparative Example 4, where the value was greater than 0.30, the copper oxide ink agglomerated, and thus reverse printing and resistance measurement could not be performed.

[0371] [Laser burning]

[0372] The copper oxide ink of Example 1 was bar-coated on a PET substrate to a predetermined thickness (800 nm), and dried at room temperature for 10 minutes, thereby obtaining a sample A in which a coating layer was formed on PET.

[0373] Using a galvano scanner, laser light (wavelength 445 nm, output 1.1 W, continuous wave oscillation (Continuous Wave: CW) was irradiated onto sample A while moving the focus position at a maximum speed of 300 mm / min, thereby obtaining a conductive film containing copper with a size of 25 mm×1 mm. The resistance was 20 μΩcm. A conductive film was also produced during laser firing.

[0374] <Experimental Example 2>

[0375] (Production of Copper Oxide Particle Dispersion)

[0376] The preparation of the dispersion comprising copper oxide particles is carried out as follows.

[0377] (Production Example 1)

[0378] 391.5 g of copper (II) acetate monohydrate (Wako Pure Chemical Industries, Ltd.) was dissolved in a mixed solvent of 3670 g of water and 1696 g of 1,2-propylene glycol (Wako Pure Chemical Industries, Ltd.), and 114 g of hydrazine monohydrate (Wako Pure Chemical Industries, Ltd.) was added and stirred. The mixture was then separated into a supernatant and a precipitate by centrifugation.

[0379] To 200 g of the obtained precipitate, 27.6 g of DISPERBYK-118 (manufactured by BYK Chemicals) and 490 g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) were added as a dispersant, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere.

[0380] Next, the concentration by UF membrane module and the dilution by ethanol were repeated, and the dilution by terpineol and the concentration by UF membrane were further repeated to obtain a dispersion S1 (225.4 g) containing 124 g of cuprous oxide with an average secondary particle size of 10 nm. The average secondary particle size was measured by the accumulation method using FPAR-1000 manufactured by Otsuka Electronics. The same is true for the following manufacturing examples 2 to 15 and comparative manufacturing examples 1 to 3.

[0381] (Production Example 2)

[0382] 391.5 g of copper (II) acetate monohydrate (Wako Pure Chemical Industries, Ltd.) was dissolved in 10880 g of water, and 114 g of hydrazine monohydrate (Wako Pure Chemical Industries, Ltd.) was added and stirred, followed by centrifugal separation into a supernatant and a precipitate.

[0383] Thereafter, the same mixing amount, conditions and process as in Production Example 1 were used to obtain a dispersion S2 (225.4 g) containing 124 g of cuprous oxide having an average secondary particle size of 33 nm.

[0384] (Production Example 3)

[0385] Dispersion S3 (204.7 g) containing 124 g of cuprous oxide having an average secondary particle size of 10 nm was obtained by the same mixing amounts, conditions and procedures as in Production Example 1 except that 6.9 g of DISPERBYK-118 (manufactured by BYK Chemicals) was used as a dispersant.

[0386] (Production Example 4)

[0387] Dispersion S4 (239.2 g) containing 124 g of cuprous oxide having an average secondary particle size of 10 nm was obtained by the same mixing amounts, conditions and procedures as in Production Example 1 except that 41.4 g of DISPERBYK-118 (manufactured by BYK Chemicals) was used as a dispersant.

[0388] (Production Example 5)

[0389] Dispersion S5 (204.7 g) containing 124 g of cuprous oxide having an average secondary particle size of 33 nm was obtained by the same mixing amounts, conditions and procedures as in Production Example 2 except that 6.9 g of DISPERBYK-118 (manufactured by BYK Chemicals) was used as a dispersant.

[0390] (Production Example 6)

[0391] Dispersion S6 (239.2 g) containing 124 g of cuprous oxide having an average secondary particle size of 33 nm was obtained by the same mixing amounts, conditions and procedures as in Production Example 2 except that 41.4 g of DISPERBYK-118 (manufactured by BYK Chemicals) was used as a dispersant.

[0392] (Production Example 7)

[0393] Dispersion S7 (201.9 g) containing 124 g of cuprous oxide having an average secondary particle size of 10 nm was obtained by the same mixing amounts, conditions and procedures as in Production Example 1 except that 4.1 g of DISPERBYK-118 (manufactured by BYK Chemicals) was used as a dispersant.

[0394] (Production Example 8)

[0395] Dispersion S8 (253.0 g) containing 124 g of cuprous oxide having an average secondary particle size of 10 nm was obtained by the same mixing amounts, conditions and procedures as in Production Example 1 except that 55.2 g of DISPERBYK-118 (manufactured by BYK Chemicals) was used as a dispersant.

[0396] (Production Example 9)

[0397] Dispersion S9 (201.9 g) containing 124 g of cuprous oxide having an average secondary particle size of 33 nm was obtained by the same mixing amounts, conditions and procedures as in Production Example 2 except that 4.1 g of DISPERBYK-118 (manufactured by BYK Chemicals) was used as a dispersant.

[0398] (Production Example 10)

[0399] Dispersion S10 (280.6 g) containing 124 g of cuprous oxide having an average secondary particle size of 33 nm was obtained by the same mixing amounts, conditions and procedures as in Production Example 2 except that 82.9 g of DISPERBYK-118 (manufactured by BYK Chemicals) was used as a dispersant.

[0400] (Production Example 11)

[0401] 101.4 g of terpineol was added to 124 g of cuprous oxide having a particle size of 150 nm, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere to obtain a dispersion S11 (225.4 g).

[0402] (Production Example 12)

[0403] Dispersion S12 (225.4 g) containing 124 g of cuprous oxide was obtained by the same mixing amounts, conditions and process as in Production Example 1 except that γ-butyrolactone was used instead of terpineol.

[0404] (Production Example 13)

[0405] Dispersion S13 (225.4 g) containing 124 g of cuprous oxide was obtained by the same mixing amounts, conditions and process as in Production Example 1 except that cyclohexanol was used instead of terpineol.

[0406] (Production Example 14)

[0407] Dispersion S14 (225.4 g) containing 124 g of cuprous oxide was obtained by the same mixing amounts, conditions and process as in Production Example 1 except that ethylene glycol monoethyl ether acetate was used instead of terpineol.

[0408] (Production Example 15)

[0409] Dispersion S15 (225.4 g) containing 124 g of cuprous oxide was obtained by the same mixing amounts, conditions and process as in Production Example 1 except that tetralin was used instead of terpineol.

[0410] (Comparative Manufacturing Example 1)

[0411] 27.6 g of DISPERBYK-118 (manufactured by BYK Chemicals) and 73.8 g of terpineol were added to 124 g of cuprous oxide having an average secondary particle size of 150 nm, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere to obtain a dispersion H1 (225.4 g).

[0412] (Comparative Manufacturing Example 2)

[0413] Dispersion H2 (225.4 g) containing 124 g of cuprous oxide was obtained by the same mixing amounts, conditions and process as in Production Example 1 except that toluene was used instead of terpineol.

[0414] (Comparative Manufacturing Example 3)

[0415] Dispersion H3 (225.4 g) containing 124 g of cuprous oxide was obtained by the same mixing amounts, conditions and process as in Production Example 1 except that butanol was used instead of terpineol.

[0416] (Examples 6 to 67)

[0417] To 40 g of any one of the dispersions S1 to S15 obtained in Manufacturing Examples 1 to 15, any one of the following copper particles A, B, C, D, and E was added in the amount shown in Table 2, and mixed using a rotation and revolution mixer under a nitrogen atmosphere to obtain dispersions of Examples 6 to 67. The mass ratio of these organic compounds (BYK / Cu2O) and the mass ratio of copper particles (Cu / Cu2O) are listed in Table 2.

[0418] Copper particles A: needle-shaped copper powder (average particle size 4.7 μm)

[0419] Copper particles B: dendritic copper powder (average particle size 14.5 μm)

[0420] Copper particles C: flaky copper powder (1400YP manufactured by Mitsui Mining & Smelting Co., Ltd.: average particle size 4.9 μm)

[0421] Copper particles D: spherical copper powder (average particle size 1 μm)

[0422] Copper particles E: spherical copper powder (average particle size 5 μm)

[0423] The dispersions of Examples 6 to 67 were printed on a paper substrate in a linear pattern by screen printing, and then heated and fired at 1.5 kW for 420 seconds using a microwave plasma burner to form a conductive film with a width of 1 mm, a length of 100 mm, and a thickness of 16 μm on the paper substrate.

[0424] The dispersions of Examples 6 to 67 were evaluated for dispersion stability and continuous printing properties. In addition, the conductive films obtained using the dispersions of Examples 6 to 67 were measured for initial resistance, resistance stability, and solderability. The results are shown in Table 2.

[0425] The dispersion stability was evaluated as follows.

[0426] A···The period of time that the dispersion can be screen printed is 20 days or more after preparation

[0427] B. The period of time that the dispersion can be screen printed after preparation is 5 days or more and less than 20 days

[0428] C···The period of time that the dispersion can be screen printed is less than 5 days after preparation

[0429] Regarding the continuous printing property, screen printing was continuously performed multiple times on the paper substrate, and the case where the number of continuous screen printing was 5 or more times was evaluated as A, and the case where the number of continuous screen printing was less than 5 times was evaluated as B. The results are shown in Table 2.

[0430] Initial resistance is the volume resistivity of the conductive film just after firing (unit: 10 -5 Ω·cm). The volume resistivity was measured using a low resistivity meter Loresta GP produced by Mitsubishi Chemical Corporation.

[0431] The resistance stability is represented by the ratio of the volume resistivity of the conductive film 100 days after firing to the volume resistivity of the conductive film immediately after firing.

[0432] In the welding test, a flux-cored wire (60% tin and 40% lead) was welded on a paper substrate formed with a conductive film using a soldering iron, and the solder portion was visually observed. The weldability was evaluated as follows. The surface of the conductive film was completely wetted with solder, and the state in which no repulsion was confirmed was evaluated as "A: No tin shrinkage", and the state in which repulsion was confirmed despite a small amount was evaluated as "B: There was tin shrinkage".

[0433] (Examples 68 to 70)

[0434] The dispersions of Examples 6, 8, and 44 were printed on a paper substrate in a linear pattern by screen printing, and then a photo-burning device Pulse Forge 1300 manufactured by NovaCentrix was used to burn the dispersions at an energy density of 7 J / cm 2 , pulse width of 8 milliseconds for light burning, forming a conductive film with a width of 1 mm, a length of 100 mm and a film thickness of 16 μm on the paper substrate.

[0435] The conductive films obtained using the dispersions of Examples 68 to 70 were subjected to measurement of initial resistance and resistance stability and a welding test.

[0436] The surface roughness of the conductive film surface obtained using the dispersion of Example 6 was measured and found to be 1340 nm. The surface roughness of the conductive film surface was measured by the following method.

[0437] Measurement method: Based on JIS B0601 2013 (ISO25178-2: 2012)

[0438] Measurement equipment: KEYENCE Co., Ltd. laser microscope VK-X250, lens magnification 150 times

[0439] The surface shape of the conductive film was measured at the center of the electrode using a laser microscope, and the arithmetic mean height of the entire screen of the concave-convex image obtained using the laser microscope was calculated as the surface roughness.

[0440] (Comparative Example 5)

[0441] 98 g of ethanol was added to 40 g of the precipitate obtained in the same mixing amount, conditions and process as in Production Example 1, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere, but the mixture was not dispersed.

[0442] (Comparative Example 6)

[0443] 98 g of ethanol was added to 40 g of the precipitate obtained in the same mixing amount, conditions and process as in Production Example 2, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere, but the mixture was not dispersed.

[0444] (Comparative Example 7)

[0445] 98 g of terpineol was added to a mixture of the precipitate and ethanol obtained in the same mixing amount, conditions and process as in Production Example 1, and dispersed using a homogenizer under a nitrogen atmosphere, but the mixture was not dispersed.

[0446] (Comparative Example 8)

[0447] 98 g of terpineol was added to a mixture of the precipitate and ethanol obtained in the same mixing amount, conditions and process as in Production Example 2, and dispersed using a homogenizer under a nitrogen atmosphere, but the mixture was not dispersed.

[0448] (Comparative Examples 9 to 11)

[0449] Copper particles F: 88 g of spherical copper powder (average particle size 200 μm) were added to 40 g of the dispersions H1, S1 and S2 obtained in Comparative Manufacturing Example 1 and Manufacturing Examples 1 and 2, and mixed using a self-rotating revolution mixer under a nitrogen atmosphere to obtain dispersions of Comparative Examples 9 to 11. The mass ratio of these organic compounds (BYK / Cu2O) and the mass ratio of copper particles (Cu / Cu2O) are listed in Table 2.

[0450] Using the dispersions of Comparative Examples 9 to 11, conductive films were formed on paper substrates under the same conditions as in Examples 6 to 67. The dispersions of Comparative Examples 9 to 11 were evaluated for dispersion stability and continuous printing properties. In addition, the conductive films obtained using the dispersions of Comparative Examples 9 to 11 were measured for initial resistance, resistance stability, and solderability. The results are listed in Table 2.

[0451] (Comparative Example 12)

[0452] 400 g of diethylene glycol was added to 200 g of a precipitate obtained in the same mixing amount, conditions and process as in Production Example 1, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere to obtain a dispersion containing cuprous oxide.

[0453] To 40 g of the dispersion was added 88 g of copper particles D: spherical copper powder (average particle size 1 μm), and the mixture was mixed using an autorotation-revolution mixer in a nitrogen atmosphere to obtain a dispersion of Comparative Example 12.

[0454] An attempt was made to print a linear pattern on a paper substrate using the dispersion of Comparative Example 12 by screen printing, but the copper particles aggregated rapidly and printing could not be performed.

[0455] (Comparative Example 13)

[0456] 18 g of terpineol was added to the copper particles B (88 g), and mixed with a rotary mixer under a nitrogen atmosphere to obtain a dispersion of Comparative Example 13. This dispersion did not contain cuprous oxide particles, and thus, as shown in Table 2, the copper particle mass ratio (Cu / Cu2O) was zero.

[0457] Using the dispersion of Comparative Example 13, a conductive film was formed on a paper substrate under the same conditions as in Examples 6 to 67. The initial resistance and resistance stability of the conductive film obtained using the dispersion of Comparative Example 13 were measured. The results are shown in Table 2.

[0458] (Comparative Example 14)

[0459] Dispersion S11, 40 g obtained in Preparation Example 11 was mixed in a nitrogen atmosphere using a rotation and revolution mixer without adding copper particles to obtain dispersion of Comparative Example 14. As shown in Table 2, the copper particle mass ratio (Cu / Cu2O) of these dispersions was zero.

[0460] Using the dispersion of Comparative Example 14, a conductive film was formed on a paper substrate under the same conditions as in Examples 6 to 67. The initial resistance and resistance stability of the conductive film obtained using the dispersion of Comparative Example 14 were measured. The results are shown in Table 2.

[0461]

[0462]

[0463]

[0464]

[0465]

[0466] Table 2 shows that when copper particles A: needle-shaped copper powder (average particle size 4.7 μm), copper particles B: dendritic copper powder (average particle size 14.5 μm), copper particles C: flaky copper powder (average particle size 4.9 μm), copper particles D: spherical copper powder (average particle size 1 μm), copper particles E: spherical copper powder (average particle size 5 μm), and DISPERBYK-118 was used as an example of an organic compound having a phosphate group, the dispersions of Examples 6 to 67 obtained were excellent in dispersion stability and continuous printability. In addition, it was confirmed that the conductive films of Examples 6 to 67 obtained by printing a linear pattern by screen printing using the dispersions of Examples 6 to 67 and performing a firing treatment had low initial resistance, excellent resistance stability, and excellent solderability.

[0467] It is confirmed from these results that the dispersion of the dispersion containing copper oxide particles with an average secondary particle size of 1 nm or more and 50 nm or less, copper particles with a particle size of 0.1 μm or more and 100 μm or less, and an organic compound with a phosphoric acid group has excellent dispersion stability, and can be screen printed even after a long period of time after the dispersion is made. It is also known that the conductive film obtained using such a dispersion has a low initial resistance and excellent resistance stability. It is also known that the weldability is excellent. It is also known that the mass ratio of the organic compound with a phosphoric acid group to the mass of copper oxide is preferably 0.0050 or more and 0.40 or less, and more preferably 0.0050 or more and 0.30 or less.

[0468] From these results, it was confirmed that in Examples 6 to 67 obtained by adding copper particles A: needle-shaped copper powder, copper particles B: dendrite-shaped copper powder, and copper particles C: flaky copper powder to dispersions S1 to S15 containing cuprous oxide particles, the conductive films obtained by printing linear patterns using the dispersions by screen printing and performing a firing treatment had low initial resistance and excellent resistance stability. The weldability was also excellent. The same was true for Examples 68 to 70.

[0469] As described above, the conductive film obtained using the dispersion of the example has excellent solderability. This confirmed that the occurrence of defects in the solder joint between the conductive film and the joined portion of the electronic component can be prevented, and the substrate with electronic components can be manufactured with a high yield.

[0470] Furthermore, as can be seen from the evaluation of the initial resistance and resistance stability of the conductive film, it was confirmed that a substrate with an electronic component having excellent performance was obtained.

[0471] In addition, it was confirmed that in Examples 53 to 55 using dispersion S11, screen printing was possible, and the initial resistance was low and the resistance stability was excellent, even though the dispersant (DISPERBYK-118) was not used. It was also confirmed that the weldability was excellent. Thus, it was confirmed that the use of the dispersant did not affect the effect of the dispersion of this embodiment.

[0472] On the other hand, the dispersions of Comparative Examples 5 to 8, which did not use DISPERBYK-118 (an example of an organic compound having a phosphate group), could not be screen-printed.

[0473] The dispersion of Comparative Example 9 containing cuprous oxide particles having an average secondary particle size of 150 nm and copper particles F having a particle size of 200 μm: spherical copper powder had a dispersion stability rating of C. It was also confirmed that the conductive film obtained using the dispersion had low initial resistance and excellent solderability, but poor resistance stability.

[0474] The dispersions of Comparative Examples 10 and 11 in which copper particles F: spherical copper powder with a particle size of 200 μm were added to the dispersions S1 and S2 had dispersion stability evaluation B. However, it was confirmed that the conductive films obtained using these had low initial resistance and excellent solderability, but poor resistance stability.

[0475] Screen printing was not possible in Comparative Example 12. In addition, when only cuprous oxide particles or copper particles were included as in Comparative Examples 13 and 14, screen printing was possible, but the initial resistance was high and the resistance stability was low.

[0476] (Comparative Examples 15 and 16)

[0477] The above copper particles A (88 g) were added to 40 g of the dispersions H2, H3, and 40 g obtained in Comparative Examples 2 and 3, and mixed using a rotation and revolution mixer under a nitrogen atmosphere to obtain dispersions of Comparative Examples 15 and 16. The copper particle mass ratios (Cu / Cu2O) of these dispersions are shown in Table 2.

[0478] Using the dispersions of Comparative Examples 15 and 16, conductive films were formed on paper substrates under the same conditions as in Examples 6 to 67. The conductive films obtained using the dispersions of Comparative Examples 15 and 16 were evaluated for initial resistance. In addition, the dispersions of Comparative Examples 15 and 16 were evaluated for continuous printing properties. The results are listed in Table 2.

[0479] As can be seen from Table 2, it was confirmed that the conductive film obtained by adding copper particles A: needle-shaped copper powder, copper particles B: dendritic copper powder and copper particles C: flaky copper powder to dispersions S11 to S15 containing cuprous oxide particles using terpineol, γ-butyrolactone, cyclohexanol, ethylene glycol monoethyl ether acetate and tetralin as dispersion media and printing a linear pattern by screen printing using the obtained dispersions of Examples 53 to 67 and performing a firing treatment had a low initial resistance. In addition, the evaluation of the continuous printability of the above dispersion was A.

[0480] In Comparative Examples 15 and 16, toluene and butanol were used as dispersion media, and as shown in Table 2, the initial resistance was low and the continuous printability was evaluated as B. These results confirmed that terpineol, γ-butyrolactone, cyclohexanol, ethylene glycol monoethyl ether acetate, and tetralin contribute to the improvement of continuous printability.

[0481] It can be seen from this that, as shown in Examples 53 to 67 disclosed in Table 2, by using a dispersion containing cuprous oxide particles and needle-shaped, dendritic or scaly copper particles, containing any one of terpineol, γ-butyrolactone, cyclohexanol, ethylene glycol monoethyl ether acetate and tetralin as a dispersion medium, and containing an organic compound having a phosphate group, a conductive film with low initial resistance and excellent continuous printability can be obtained by a screen printing method.

[0482] (Comparative Example 17)

[0483] A linear pattern was printed on a paper substrate by screen printing using copper paste CP-1P manufactured by NOF Corporation that does not contain cuprous oxide particles and does not contain an organic compound having a phosphate group. Subsequently, plasma firing was performed under the same conditions as in Examples 6 to 67 to form a conductive film on the paper substrate.

[0484] The obtained conductive film of Comparative Example 17 was subjected to a soldering test, but tin shrinkage occurred, and the evaluation was B. The surface roughness of the conductive film was also measured, and the surface roughness was 858 nm.

[0485] It can be confirmed from Table 2 that when copper particles A: needle-shaped copper powder, copper particles B: dendritic copper powder and copper particles C: flaky copper powder are added to dispersions S1, 3, 4, 7, and 8 containing cuprous oxide particles, the conductive film obtained by printing a linear pattern using the dispersion by screen printing and performing a firing treatment has a low initial resistance, high resistance stability, and excellent weldability.

[0486] In Comparative Example 17, although screen printing was possible, solderability was evaluated as B, indicating poor solderability. This result indicates that screen printing was possible by using a copper paste, but organic components that cause tin shrinkage remained in the conductive film after plasma firing, resulting in poor solderability.

[0487] Claim 1 is based on Experimental Example 1. Claims 2 and 3 are based on Experimental Example 2.

[0488] It should be noted that the present invention is not limited to the above-described embodiments and examples. The embodiments and examples may be modified based on the knowledge of those skilled in the art, and the embodiments and examples may be combined arbitrarily, and such modifications are also included in the scope of the present invention.

[0489] This application is based on Japanese Patent Application Nos. 2017-51568, 2017-51569, 2017-51570, 2017-51571, 2017-51572 filed on March 16, 2017, 2017-145188 filed on July 27, 2017, and 2018-23239 and 2018-23242 filed on February 13, 2018. The contents of these are all incorporated herein.

Claims

1. A dispersion, characterized in that The dispersion comprises copper oxide, a dispersant, and a reducing agent. The content of the reducing agent is within the range of the following formula (1): The content of the dispersant is within the range of the following formula (2): The number average molecular weight of the dispersant is 300 to 30,000. 0.0001≦(reducing agent mass / copper oxide mass)≦0.10 (1) 0.0050≦(dispersant mass / copper oxide mass)≦0.30 (2) The dispersant comprises a phosphorus-containing organic substance, The particle size of the copper oxide is not less than 1 nm and not more than 50 nm. The reducing agent comprises at least one selected from the group consisting of hydrazine, hydrazine hydrate, sodium, carbon, potassium iodide, oxalic acid, iron (II) sulfide, sodium thiosulfate, ascorbic acid, tin (II) chloride, diisobutylaluminum hydride, formic acid, sodium borohydride and sulfite.

2. The dispersion according to claim 1, characterized in that The acid value (mgKOH / g) of the dispersant is 20 or more and 130 or less.

3. The dispersion according to claim 1, wherein The acid value (mgKOH / g) of the dispersant is 30 or more and 100 or less.

4. The dispersion according to claim 1, characterized in that The difference between the amine value (mgKOH / g) and the acid value of the dispersant, that is, amine value minus acid value, is -50 or more and 0 or less.

5. The dispersion according to claim 1, characterized in that The copper oxide is cuprous oxide.

6. The dispersion according to claim 1 or 2, characterized in that The dispersion further includes a dispersion medium, and the dispersion medium includes a monoalcohol having 10 or less carbon atoms.

7. A method for manufacturing a structure with a conductive pattern, characterized in that: The manufacturing method comprises the following steps: A step of applying the dispersion according to any one of claims 1 to 6 on a substrate to form a coating film, and The step of irradiating the coating film with laser light to form a conductive pattern on the substrate.

8. The method for manufacturing a structure with a conductive pattern according to claim 7, wherein: After the coating film is formed on a transfer body, the coating film is transferred from the transfer body to the substrate to form the coating film on the substrate.

9. The method for manufacturing a structure with a conductive pattern according to claim 7, wherein: The conductive pattern is an antenna.

10. The method for manufacturing a structure with a conductive pattern according to claim 7, wherein: The manufacturing method further includes the step of forming a solder layer on a portion of the surface of the conductive pattern.

11. A method for manufacturing a structure with a conductive pattern, characterized in that: The manufacturing method comprises the following steps: A step of applying the dispersion according to any one of claims 1 to 6 on a substrate in a desired pattern to form a coating film; and The coating film is fired to form a conductive pattern on the substrate.

12. The method for manufacturing a structure with a conductive pattern according to claim 11, wherein: The firing treatment is performed by generating plasma in an atmosphere containing a reducing gas.

13. The method for manufacturing a structure with a conductive pattern according to claim 11, wherein: The firing treatment is performed by a light irradiation method.

14. The method for manufacturing a structure with a conductive pattern according to claim 11, wherein: The calcination treatment is performed by heating the coating film at 100° C. or higher.

15. The method for producing a structure with a conductive pattern according to any one of claims 11 to 14, wherein: The dispersion is applied by an aerosol method to form the desired pattern.

16. The method for producing a structure with a conductive pattern according to any one of claims 11 to 14, wherein: The dispersion was applied by screen printing.

17. The method for producing a structure with a conductive pattern according to any one of claims 11 to 14, wherein: After the coating film is formed on a transfer body, the coating film is transferred from the transfer body to the substrate to form the coating film on the substrate.

18. The method for manufacturing a structure with a conductive pattern according to any one of claims 11 to 14, characterized in that: The manufacturing method has the following steps: After applying the dispersion to a transfer body, a convex portion is brought into contact with the transfer body to remove unnecessary dispersion to form a desired pattern on the surface of the transfer body; and A step of transferring the desired pattern to the substrate by bringing the substrate into contact with a surface of the transfer body.

19. The method for producing a structure with a conductive pattern according to any one of claims 11 to 14, wherein: The conductive pattern is an antenna.

20. The method for manufacturing a structure with a conductive pattern according to claim 19, wherein: The conductive pattern is in a grid shape.

21. The method for producing a structure with a conductive pattern according to any one of claims 11 to 14, wherein: The manufacturing method further includes the step of forming a solder layer on a portion of the surface of the conductive pattern.

22. The method for manufacturing a structure with a conductive pattern according to claim 21, wherein: The electronic component is soldered onto the conductive pattern through the solder layer by a reflow method.